Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

A discontinuous Bubnov-Galerkin spectral element spatial discretisation of the first-order form of the neutron transport equation using a discrete ordinate angular discretisation with multidimensional anisotropic dispersion and dissipation analysis - J.I. Mitchell; M.D. Eaton; R.C. Moura; C. Jones; S.G. Wilson; C. Latimer; J. Kópházi (Annals of Nuclear Energy, 2026)

The pH-responsive interfacial behaviour of rice bran nanocellulose and its impact on Pickering emulsion stability and creaming - K C Yadav; Bhesh Bhandari; Jaquie Mitchell; Sangeeta Prakash (Food Research International, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Early ecological trajectories of native woodlands established under Ireland’s Native Woodland Scheme - Kate Harrington; Fraser J.G. Mitchell; Jane C. Stout (Forest Ecology and Management, 2026)

The microbial communities of a tomato crop grown in Veggie under different lighting regimes on the International Space Station - Cory J. Spern; Mary E. Hummerick; Christina LM Khodadad; Cristiana J. Morales; Anirudha R. Dixit; Lashelle E. Spencer; Cary A. Mitchell; Robert C. Morrow; Raymond M. Wheeler; Gioia D. Massa (Life Sciences in Space Research, 2026)

Application of the Total Nutrient Index as a Precision Nutrition Tool to Address Dietary Recommendations Across the Life Course - Alexandra E. Cowan-Pyle; Janet A. Tooze; Lindsay M. Reynolds; Jaime J. Gahche; Johanna T. Dwyer; Diane C. Mitchell; Raymond J. Carroll; Bani K. Mallick; Regan L. Bailey (Journal of the Academy of Nutrition and Dietetics, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Caledochytrium aldermanii gen. Et sp. nov.; a new Labyrinthulomycete displaying a novel reproductive strategy - Jane L. Polglase; Peter C. Morris; Stephen W. Feist; Wilfrid J. Mitchell; Fiona Strachan; Kirsty A. Fraser; James R. Iremonger; Elisabeth A. Dyrynda; Alastair R. Lyndon; Lydia A. Brown (Protist, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

Ancestry informative genetic variants associated with tobacco metabolic and detoxification capacity measured by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) among smokers - Oladimeji Lanade; Zhongxuan He; Yan Zhou; Elizabeth Blackman; Denise Gibbs; Sharon Harrison; Karthik Devarajan; Mark Andrake; Roland L. Dunbrack; Gerald Nkogbu; Aditi Wagh; Michael Slifker; et al. (Archives of Toxicology, 2026)
Tobacco use remains the leading preventable cause of cancer mortality worldwide, with marked disparities in cancer incidence and outcomes across racial and ethnic groups. This study investigates the genetic determinants of tobacco carcinogen metabolism among smokers, focusing on ancestry-informative markers (AIMs) near genes involved in metabolic activation (Phase I), detoxification (Phase II), and transport (Phase III) of tobacco-specific carcinogens. Using data from 274 smokers recruited in the United States and the Caribbean, we measured urinary NNAL (a metabolite of NNK) to classify metabolic phenotypes and performed genotyping with a customized array enriched for AIMs. Most participants (94%) were classified as poor metabolizers of NNAL, with a higher prevalence among Black/African American smokers. Multivariable analyses, after adjusting for age, sex, assay batch, and number of cigarettes smoked per day, identified 14 AIMs near Phase I, II, and III pathway genes significantly associated with NNAL metabolizer phenotype, with African ancestry alleles conferring increased odds of poor metabolism. Functional annotation revealed that most significant AIMs overlapped regulatory regions, and the CYP3A5 rs776746 variant demonstrated structural disruption likely to impair enzymatic activity. Majority of participants had high African ancestry and were poor NNAL metabolizers, consistent with the observed association between African ancestry and poor NNAL metabolism. These findings highlight the biological basis for tobacco-related cancer disparities and underscore the importance of integrating genetic ancestry and metabolic phenotyping in risk assessment and personalized prevention strategies for tobacco-associated cancers.

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mechanistic insights into the interfacial rheology of cellulose nanofibers from rice bran for stabilising pickering emulsions - Yadav K C; Jaquie Mitchell; Bhesh Bhandari; Sangeeta Prakash (Journal of Food Engineering, 2026)

Localised effects of sparse natural tree colonisation on soil physicochemical properties - Naomi C. Housego; Thomas C. Parker; Lorna E. Street; Elena I. Vanguelova; Ruth J. Mitchell (Trees, 2026)
Tree establishment via natural colonisation is increasing globally, due to treeline expansion under climate change, and changing land management practices, such as reduced grazing pressure, land abandonment, and initiatives to increase tree cover such as restoration and rewilding. Natural colonisation of organo-mineral soils at high densities is associated with altered soil physicochemical properties, with consequences for ecosystem services such as soil carbon stocks, biodiversity, and hydrology. But whether sparse natural colonisation of organo-mineral soils has similar effects on soil physicochemical properties to dense natural colonisation is not known. To investigate the effects of sparse natural colonisation on organo-mineral soils, we measured soil physicochemical properties at increasing distances up to 8 metres from single, native ( Pinus sylvestris L. or Betula spp.) naturally colonised trees in Cairngorms, Scotland, UK. Distance from single, native, naturally colonised trees was associated with increased soil moisture and decreased carbon-to-nitrogen and carbon-to-phosphorus ratios, but not associated with changes in bulk density, decomposition rates, or pH, in the organic horizon of organo-mineral soils. Sparse natural colonisation (in this study, 43 trees ha − 1 ) of organo-mineral soils has some, localised effects on the physicochemical properties of the organic horizon, which might affect biodiversity and hydrology in patches around trees. These effects did not extend beyond 2 metres distance from the trees. This suggests that early, sparse tree colonisation has minimal impacts on soil physicochemical properties at the ecosystem scale.

Crop mixtures: yield responses to climate and management and impacts on seed and soil chemical composition in a Scottish-based study - R. Brooker; R. J. Pakeman; R. L. Hewison; C. Mitchell; A. C. Newton; R. Neilson; S. Raubach; P. D. Shaw; S. Verrall; A. J. Karley (Plant and Soil, 2026)
Introduction Crop mixtures can be an important part of the toolkit for maintaining crop production while addressing the climate and nature crises. However, uncertainties around some issues may prevent their uptake. Research question This study addressed several uncertainties, specifically the response of mixture yields to climate and management, and the impacts of mixed cropping on seed chemical composition, soil carbon and nutrients. Materials and methods We undertook 32 intercropping trials between 2020 and 2022 on both commercial and research farms. These varied in design, management and crop combinations, with mixture choice often determined by farmers. We assessed multiple responses including yield, weed cover, and seed and soil chemical composition. Results and conclusions When compared to monocultures, yield gains from growing a crop mixture were roughly 20% based on Crop Performance Ratio (CPR). We found limited impacts of mixture diversity and composition on seed chemical composition, influences of management on weed control, and enhanced crop mixture performance under cooler conditions with lower rainfall. We also found varying mixture performance depending on mixture composition. Importantly, irrespective of management, climate, and composition effects, crop mixtures always performed at least as well as expectations based on monocultures. Even without further refinement from, for example, targeted breeding, crop mixtures provide reliable crops without yield losses or (for parameters tested) substantial changes in seed chemistry. However, detected reductions in organic matter in upper soil layers indicate a priority for future research is understanding crop mixture impacts on soil carbon dynamics in both shallow and deep soils.

An epigenetic switch in vascular phenotype augments anti-tumor immunity - Dae Joong Kim; Mitchell McGinty; Swetha Anandh; Caroline Riedstra; Yuvraj Sethi; Melanie R. Rutkowski; Andrew C. Dudley (Angiogenesis, 2026)
The abnormal tumor vasculature can present a barrier to the infiltration of anti-tumor immune cells, which impairs immune surveillance and response to immunotherapy. Here, we show that genetically deleting the epigenetic factor DNA methyltransferase 1 ( Dnmt1 ) in endothelial cells (ECs) reduces angiogenesis while imparting profound changes to the tumor immune microenvironment (TIME), including increased proportions of CD4 + memory T cells and NK cells. Depleting CD4 + T cells, or blocking lymphocyte egress from the lymph nodes, rescues tumor growth in mice with conditional deletion of Dnmt1 in ECs ( Dnmt1 iECKO ) and dramatically shortens overall survival, whereas NK cells are dispensable. Tumors implanted in Dnmt1 iECKO mice show reduced vascular branching, elevated expression of VCAM1, increased vessel-associated T cells, and a shift in vascular specification, including increased proportions of immune-permissive post-capillary venules (PCVs) and interferon-stimulated ECs (IFN-ECs). Deleting Dnmt1 in EC cultures strikingly potentiates responses to combinations of IFNγ and TNFα and, notably, up-regulates important T-cell co-stimulatory molecules for memory CD4 + T cells, including Icosl , Cd40 , and Tnfsf4 . Finally, immune checkpoint blockade (ICB) administered to Dnmt1 iECKO mice with experimental melanoma lung metastasis reduces tumor burden, with some mice showing tumor eradication. Our findings identify endothelial Dnmt1 as a key regulator of vascular-mediated anti-tumor immunity, providing a rationale for integrating epigenetic modulation of the vasculature with cancer immunotherapy regimens.

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Managing Radiation Therapy Treatment Delivery Challenges: Impact of an Interprofessional Educational Series for Radiation Therapists and Radiation Oncology Residents - Jordan McDonald; Denise De La Cruz; Chelsea C. Pinnix; Julianna K. Bronk; Comron Hassanzadeh; Emma B. Holliday; Anna Lee; Melissa P. Mitchell; Devarati Mitra; Subha Perni; Nicolette Taku; Jillian R. Gunther (Journal of Cancer Education, 2026)

Deep drawdown of the Mediterranean during the Messinian Salinity Crisis inferred from Nile Canyon 3D seismic reflection data near Cairo, Egypt - William Bosworth; Neil C. Mitchell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High-pressure homogenised rice bran nanofibers as stabilisers in pickering emulsions: Interfacial behaviour, emulsification efficiency and oxidative stability - K C Yadav; Bhesh Bhandari; Jaquie Mitchell; Sangeeta Prakash (Bioresource Technology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

OnabotulinumtoxinA Inhibits Dysregulation of Descending Pain Modulation Following Mild Traumatic Brain Injury in Mice - Robson C. Lillo Vizin; Caroline M. Kopruszinski; Janice N. Oyarzo; David W. Dodick; Ron S. Broide; Amy D. Brideau-Andersen; Mitchell F. Brin; Trent Anderson; Edita Navratilova; Frank Porreca (Toxicon, 2026)

Sequential Administration of TrenibotulinumtoxinE and OnabotulinumtoxinA for Glabellar Lines: A Phase 1 Evaluation - C. William Hanke; Joely Kaufman-Janette; Steve H. Dayan; Grace West; Amy S. Weitzenfeld; Jie Shen; Stephanie Manson Brown; Mitchell F. Brin; Mitalee Tamhane (Toxicon, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Changes in Adolescent Diet Quality During the Middle to High School Transition - Jessica E. Decker; Knashawn Morales; Emily Moll; Sana Husain; Mary Ellen Vajravelu; Erica C. Jansen; Babette S. Zemel; Jonathan A. Mitchell (Journal of Nutrition Education and Behavior, 2026)

Legacy effects of cover crops on weed biomass and yield of the subsequent corn crop - Barbara Baraibar; Brosi A. Bradley; Mitchell C. Hunter; Charles M. White; Denise M. Finney; Jason P. Kaye; Megan E. Schipanski; David A. Mortensen (European Journal of Agronomy, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Pining for diversity: Does greater tree species diversity enhance the resilience of associated biodiversity and ecosystem functioning in Pinus sylvestris forests? - R.J. Mitchell; S.D. Albon; P.E. Bellamy; C. Cameron; L. Cocks; C.J. Ellis; N.G. Hodgetts; C. Johnstone; C. Nichols; J.A. Stockan; A.F.S. Taylor (Forest Ecology and Management, 2026)

The Peripheral Epigenome Predicts White Matter Volume Contingent on Developmental Stage: An ECHO Study - Taena Hanson; Sophie Spencer; Samantha A. Harker; Fatoumata Barry; Jennifer Beauchemin; B. Blair Braden; Phoebe Burton; Viren D’sa; Daphne Koinis-Mitchell; Sarah E. Mennenga; Sean C. L. Deoni; Candace R. Lewis (Molecular Neurobiology, 2026)

Detection of Cryptosporidium spp. and Giardia duodenalis DNA in wild deer in Scotland - Paul M. Bartley; Clare M. Hamilton; Jackie Thomson; Ross Bacchetti; Mairi C. Mitchell; Tom N. McNeilly; Renata Pimentel Bandeira de Melo; Adam D. Hayward; Frank Katzer; Beth Wells (Veterinary Parasitology, 2025)

Structural controls on simultaneous earthquake clustering and normal fault synchronization - F. Iezzi; C. Sgambato; G. Roberts; Z. Mildon; J. Robertson; J. Faure Walker; I. Papanikolaou; A.M. Michetti; S. Mitchell; R. Shanks; R. Phillips; K.J.W. McCaffrey; et al. (Earth and Planetary Science Letters, 2025)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Full-length mRNA sequencing resolves novel variation in 5′ UTR length for genes expressed during human CD4 T-cell activation - Cassandra R. Woolley; Julia H. Chariker; Eric C. Rouchka; Easton E. Ford; Elizabeth Hudson; Kamille M. Rasche; Caleb S. Whitley; Zachary Vanwinkle; Carolyn R. Casella; Melissa L. Smith; Thomas C. Mitchell (Immunogenetics, 2025)

A New Genus of Anacardiaceae from Madagascar - John D. Mitchell; Douglas C. Daly; Armand Randrianasolo (Brittonia, 2025)

Nubia-Arabia separation: Clues from oceanic spreading fabric in the Red Sea - Neil C. Mitchell; A.Y. Izzeldin; Ian C.F. Stewart (Gondwana Research, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

A modified-live Mannheimia haemolytica expressing Mycoplasma bovis EFTu and Hsp70 induced systemic and mucosal antibody responses in American bison but failed to fully protect against Mycoplasma bovis challenge. - Bryan S. Kaplan; Rohana P. Dassanayake; Bradley O. Chriswell; William D. Boatwright; Steven C. Olsen; Mitchell V. Palmer; Paola M. Boggiatto; Carly R. Kanipe; Eduardo Casas; Robert E. Briggs; Fred M. Tatum (Veterinary Microbiology, 2025)

New approach methodologies for assessing developmental toxicity of pharmaceuticals: Case examples and future directions - Nicola Powles-Glover; Allen R. Kaczor; Steven Van Cruchten; Christopher J. Bowman; Kimberly C. Brannen; Claudia Demarta-Gatsi; Isabelle LeConte; Amer Jamalpoor; Fumito Mikashima; Shermaine Mitchell-Ryan; Dinesh Stanislaus; Peter Theunissen; et al. (Reproductive Toxicology, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

Ash survival and growth in response to emerald ash borer invasion in Massachusetts riparian forests: Impacts of biological control - Mitchell A. Green; Jian J. Duan; Ryan S. Crandall; Roy G. Van Driesche; Armand Martinez; Jeremy C. Andersen; Joseph S. Elkinton (Forest Ecology and Management, 2025)

Population genomics of rainforest mountain frogs (Anura: Limnodynastidae: Philoria) severely impacted by the Australian megafires - Shengyao Lin; David Newell; Nicola J. Mitchell; Stephen C. Donnellan; Michael Mahony; Liam J. Bolitho; Renee A. Catullo (Conservation Genetics, 2025)
The 2019/20 Australian megafires impacted numerous species, including six of the seven montane frog species from the genus Philoria , which are restricted to the top of mountain habitats across eastern Australian Gondwana Rainforest. Using single nucleotide polymorphisms, we examined the population structure and genetic diversity of the six Philoria species to inform conservation management and assess their capacity for post-fire recovery. Narrow-range species were confirmed as a single population for management purposes, while P. kundagungan , P. loveridgei , and P. sphagnicolus exhibit marked genetic differentiation between populations, indicating strong allopatric differentiation among populations isolated on separate mountaintops, suggesting limited natural dispersal ability. We further identify high-value genetic populations in these structured species. Populations that were heavily impacted by the fires, such as P. pughi and P. knowlesi , may face longer-term threats due to potential declines in adaptive capacity. We recommend prioritising in situ management, genetic rescue, and translocation efforts to bolster resilience in isolated populations. Updated conservation planning and targeted fire buffer management are crucial for the survival of these ancient, regionally endemic frogs in a rapidly changing climate.

The associations between playing a musical instrument and grey matter in older adults at risk for dementia: a whole-brain VBM analysis - Nicole Espinosa; Marshall A. Dalton; Hannes Almgren; Andrew C. McKinnon; Helen F. Mitchell; Zoe Menczel Schrire; Sharon L. Naismith (GeroScience, 2025)

P14-14 Advancing Predictive Carcinogenicity Assessment: Evaluating Duplex Sequencing for Early Detection of Clonal Expansion as a Biomarker - C. Mitchell (Toxicology Letters, 2025)

P12-35 From neat compounds to complex mixtures: Microphysiological systems for cardiotoxicity safety testing of botanical extracts - M. Gossmann; A. Monteiro da Rocha; S. Zhao; J. Krzykwa; C. Mitchell; J. Wu; P. Linder (Toxicology Letters, 2025)

Sex-dependent latent chilling injury changes estimates of thermal tolerance in a model insect - Mahmoud I. El-Saadi; Mitchell C. Allen; Heath A. MacMillan (Journal of Insect Physiology, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Does Home and Wild Food Procurement Enhance Food Security in High-Income Countries? - Sam Bliss; Ashley C. McCarthy; Rebecca C. Mitchell; Scott C. Merrill; Rachel E. Schattman; Janica Anderzén; Meredith T. Niles (Current Environmental Health Reports, 2025)

Heat-set gelation of milk- and fermentation-derived β-lactoglobulin variants - Zheng Pan; Remco Kornet; Sheelagh Hewitt; Alan Welman; Jeremy P. Hill; Marcel Wubbolts; Stephen Mitchell; Warren C. McNabb; Aiqian Ye; Alejandra Acevedo-Fani; Skelte G. Anema (Food Hydrocolloids, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Evaluating five shoreline change models against 40 years of field survey data at an embayed sandy beach - Oxana Repina; Rafael C. Carvalho; Giovanni Coco; José A.Á. Antolínez; Iñaki de Santiago; Mitchell D. Harley; Camilo Jaramillo; Kristen D. Splinter; Sean Vitousek; Colin D. Woodroffe (Coastal Engineering, 2025)

Climate and Emissions Benefits of Renewable Diesel: In-Use Testing of a Tier 2 Commercial Harbor Craft - Julia A. Billington; Bo Yang; Wayne Sobieralski; Christian Fehrenbacher; Gavin M. Hoch; Andrew L. Damiano; Razieh Nadafianshahamabadi; Alexander R. Mitchell; David C. Quiros (Emission Control Science and Technology, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Burn parameters affect PAH emissions at conditions relevant for prescribed fires - Karl Töpperwien; Guillaume Vignat; Alexandra J. Feinberg; Conner Daube; Mitchell W. Alton; Edward C. Fortner; Manjula R. Canagaratna; Matthias F. Kling; Mary Johnson; Kari Nadeau; Scott Herndon; John T. Jayne; et al. (Atmospheric Pollution Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Soil organic carbon and aggregate characteristics in a subtropical cotton production field as influenced by century-long crop rotation and fertility management - Yuanchang TIAN; Jim J. WANG; Shuai LIU; Zhuo WEI; Syam K. DODLA; Baoyue ZHOU; Charles C. MITCHELL; Zengqiang ZHANG (Pedosphere, 2025)

Seabed stability inferred from the 2019–2020 earthquake swarm under a volcanic cone field and slopes of Condor Seamount, Azores - Neil C. Mitchell; Fernando Tempera; Thomas A. Morrow; Joaquim Luis; Christian Hübscher; Telmo Morato (Journal of Volcanology and Geothermal Research, 2025)

Process intensification in hydrothermal liquefaction of biomass: A review - Shahin Mazhkoo; Salman Soltanian; Habeeb O. Odebiyi; Omid Norouzi; Mitchell Ubene; Aneela Hayder; Omid Pourali; Rafael M. Santos; Robert C. Brown; Animesh Dutta (Journal of Environmental Chemical Engineering, 2025)

Control performance of Amphibian Metamorphosis Assays with Xenopus laevis - James R. Wheeler; Raechel Puglisi; Adriana C. Bejarano; Zhenglei Gao; Laurent Lagadic; Scott Glaberman; Constance A. Mitchell; Natalie Burden; Valentin Mingo; Scott G. Lynn; Michelle R. Embry (Regulatory Toxicology and Pharmacology, 2025)

Adult withdrawal of long-term Benzophenone-3 treatment induces regression of mammary ductal branching in a diet-dependent manner - Calista Busch; Anastasia Kariagina; Elena Morozova; Mitchell A. Borin; Richard C. Schwartz (Food and Chemical Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An update on beverage consumption patterns and caffeine intakes in a representative sample of the US population - Diane C. Mitchell; Megan Trout; Ross Smith; Robyn Teplansky; Harris R. Lieberman (Food and Chemical Toxicology, 2025)

Inferring the relative importance of navigation and landscape effects for migratory populations using agent-based models - Mitchell J. Kendzel; Jacobus C. de Roode; Lance A. Waller (Ecological Modelling, 2025)

In situ staining with antibodies cross-reactive in pigs, cattle, and white-tailed deer facilitates understanding of biological tissue status and immunopathology - Jayne E. Wiarda; Eraldo L. Zanella; Adrienne L. Shircliff; Eric D. Cassmann; Crystal L. Loving; Alexandra C. Buckley; Mitchell V. Palmer (Veterinary Immunology and Immunopathology, 2025)

Survival and causes of mortality of introduced wild pigs in the presence of cougars - Mitchell A. Parsons; Kurt C. Vercauteren; Justin A. Dellinger; Julie K. Young (Biological Invasions, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Aquatic hazard and risk posed by four pesticides detected in waterways discharging to the Great Barrier Reef, Australia: Part 2. Hazard and risk assessment - Hannah C. Mitchell; Michael St.J. Warne; Reinier M. Mann; Catherine A. Neelamraju; Ryan D.R. Turner (Science of The Total Environment, 2024)

Next-generation marker-free transplastomic plants: engineering the chloroplast genome without integration of marker genes in Solanum tuberosum (potato) - Alessandro Occhialini; Andrew C. Reed; Stacee A. Harbison; Megan J. Sichterman; Aaron Baumann; Alexander C. Pfotenhauer; Li Li; Gabriella King; Aaron G. Vincent; Ashley D. Wise-Mitchell; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2024)

The 2020 Mw 6.6 Vernadsky transform earthquake sequence: rupture and Coulomb stress changes surrounding an oceanic core complex - Guilherme W. S. de Melo; Neil C. Mitchell; Sergey Y. Sokolov (Marine Geophysical Research, 2024)
Oceanic core complexes (OCCs) are upwards-convex areas of outcropping lower crustal or upper mantle rocks raised to the seabed by normal faults, commonly associated with weak lithologies such as serpentinites. They are common adjacent to transform valleys of slow-spreading ridges. In this paper, we analyse the September 2020, Mw 6.6 strike-slip earthquake and its two-week long aftershock sequence within the Vernadsky transform valley, using recordings from regional seismic stations. The aftershocks occurred in two phases. During the first four days, ∼ 131 events occurred east and northeast of the mainshock, overlapping an adjacent OCC complex along the northern flank of the transform valley. During the following nine days, 20 aftershocks occurred, including a Mw 5.8 event close to the OCC. To refine the locations of aftershocks, the spatial spread of the events (clustering) was refined by double-difference relocating 114 events, and five with teleseismic relative relocation. Modeling of static Coulomb stresses was carried out, based on a mainshock rupture length compatible with the 26–30 km horizontal extent of aftershocks. This revealed that the aftershocks occurred mainly in areas where static Coulomb stresses decreased, not increased. Other researchers have suggested that changes in fault strength can arise from dynamic stresses during major earthquakes, leading to seismicity in areas of decreased Coulomb stress. We explore this idea in the context of OCCs.

Dynamics of peripheral T cell exhaustion and monocyte subpopulations in neurocognitive impairment and brain atrophy in chronic HIV infection - Brooks I. Mitchell; Isabelle E. Yazel Eiser; Kalpana J. Kallianpur; Louie Mar Gangcuangco; Dominic C. Chow; Lishomwa C. Ndhlovu; Robert Paul; Cecilia M. Shikuma (Journal of NeuroVirology, 2024)
Background HIV-associated neurocognitive disorders (HAND) is hypothesized to be a result of myeloid cell-induced neuro-inflammation in the central nervous system that may be initiated in the periphery, but the contribution of peripheral T cells in HAND pathogenesis remains poorly understood. Methods We assessed markers of T cell activation (HLA-DR + CD38+), immunosenescence (CD57 + CD28-), and immune-exhaustion (TIM-3, PD-1 and TIGIT) as well as monocyte subsets (classical, intermediate, and non-classical) by flow cytometry in peripheral blood derived from individuals with HIV on long-term stable anti-retroviral therapy (ART). Additionally, normalized neuropsychological (NP) composite test z-scores were obtained and regional brain volumes were assessed by magnetic resonance imaging (MRI). Relationships between proportions of immune phenotypes (of T-cells and monocytes), NP z-scores, and brain volumes were analyzed using Pearson correlations and multiple linear regression models. Results Of N = 51 participants, 84.3% were male, 86.3% had undetectable HIV RNA < 50 copies/ml, median age was 52 [47, 57] years and median CD4 T cell count was 479 [376, 717] cells/uL. Higher CD4 T cells expressing PD-1 + and/or TIM-3 + were associated with lower executive function and working memory and higher CD8 T cells expressing PD-1 + and/or TIM-3 + were associated with reduced brain volumes in multiple regions (putamen, nucleus accumbens, cerebellar cortex, and subcortical gray matter). Furthermore, higher single or dual frequencies of PD-1 + and TIM-3 + expressing CD4 and CD8 T-cells correlated with higher CD16 + monocyte numbers. Conclusions This study reinforces evidence that T cells, particularly those with immune exhaustion phenotypes, are associated with neurocognitive impairment and brain atrophy in people living with HIV on ART. Relationships revealed between T-cell immune exhaustion and inflammatory in CD16 + monocytes uncover interrelated cellular processes likely involved in the immunopathogenesis of HAND.

Niche‐based approach to explore the impacts of environmental disturbances on biodiversity - Jarrod Sopniewski; Renee Catullo; Michelle Ward; Nicola Mitchell; Ben C. Scheele (Conservation Biology, 2024)
Globally, species are increasingly at risk from compounding threatening processes, an increasingly prominent driver of which is environmental disturbances. To facilitate effective conservation efforts following such events, methods that evaluate potential impacts across multiple species and provide landscape‐scale information are needed to guide targeted responses. Often, the geographic overlap between a disturbance and species’ distribution is calculated and then used as a proxy for potential impact. However, such methods do not account for the important influence of environmental heterogeneity throughout species’ ranges. To address this shortcoming, we quantified the effects of environmental disturbances on species’ environmental niche space. Using the Australian 2019 and 2020 Black Summer fires as a case study, we applied a niche‐centric approach to examine the potential impacts of these fires on 387 vertebrate species. We examined the utility of established and novel niche metrics to assess the potential impacts of large‐scale disturbance events on species by comparing the potential effects of the fires as determined by our various niche measures to those derived from geographic‐based measures of impact. We examined the quality of environmental space affected by the disturbance by quantifying the position in niche space where the disturbance occurred (center or margin), the uniqueness of the environmental space that was burned, and the degree to which the remaining, unburned portion of the niche differed from a species’ original prefire niche. There was limited congruence between the proportion of geographic and niche space affected, which showed that geographic‐based approaches in isolation may have underestimated the impact of the fires for 56% of modeled species. For each species, when combined, these metrics provided a greater indication of postdisturbance recovery potential than geographic‐based measures alone. Accordingly, the integration of niche‐based analyses into conservation assessments following large‐scale disturbance events will lead to a more nuanced understanding of potential impacts and guide more informed and effective conservation actions.

Past fire dynamics in sub-Saharan Africa during the last 25,000 years: Climate change and increasing human impacts - Laurent Bremond; Julie C. Aleman; Charly Favier; Olivier Blarquez; Daniele Colombaroli; Simon E. Connor; Carlos E. Cordova; Colin Courtney-Mustaphi; Abraham N. Dabengwa; Graciela Gil-Romera; William D. Gosling; Tamryn Hamilton; et al. (Quaternary International, 2024)

The Calorimetric Electron Telescope (CALET) on the International Space Station: Results from the first eight years on orbit - Y. Akaike; O. Adriani; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Direct measurements of cosmic – Ray iron and nickel with CALET on the International Space Station - O. Adriani; Y. Akaike; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Ecotoxicity threshold values for 4-hydroxychlorothalonil, carbendazim, dimethoate and methoxyfenozide in fresh and marine waters: Part 1. Derivation of threshold values - Hannah C. Mitchell; Michael St.J. Warne; Reinier M. Mann; Olivia C. King; Ryan D.R. Turner (Science of The Total Environment, 2024)

Lateglacial Interstadial to mid-Holocene stratigraphy and palynology at Pepper Arden Bottoms, North Yorkshire, UK - James B. Innes; Mairead M. Rutherford; David R. Bridgland; Ben R. Gearey; Malcolm C. Lillie; Wishart A. Mitchell; Charlotte E. O'Brien; Richard T. Jones; Gareth J. Thompson (Proceedings of the Geologists' Association, 2024)

The 2019 pumice raft forming eruption of Volcano-F (Volcano 0403–091) and implications for hazards posed by submerged calderas - Isobel A. Yeo; Iona M. McIntosh; Scott E. Bryan; Kenichiro Tani; Matthew Dunbabin; Katherine J. Dobson; Samuel J. Mitchell; Patrick C. Collins; Michael A. Clare; Henrietta Cathey; Isikeli Duwai; Philipp A. Brandl; et al. (Journal of Volcanology and Geothermal Research, 2024)

Examining the sensitivity of ozone to NOx and VOCs in the Salt Lake City urban region from spatiotemporal patterns observed using stationary and mobile observations collected from a light-rail public transit platform - Andres Gonzalez; Derek Mallia; John C. Lin; Logan Mitchell; Taylor Y. Wilmot; Nancy Daher; Mark Sghiatti; Colin Harkins (Atmospheric Environment, 2024)

P06-11 A vision for the use of molecular points of departures (PODs) for chemical testing - K. Tilmant; C. Mitchell (Toxicology Letters, 2024)

Contourite-like deposits suggest stronger-than-present circulation in the Plio-Pleistocene Red Sea - Neil C. Mitchell; Marco Ligi; Jonas Preine; Diederik Liebrand; Moamen Ali; Alessandro Decarlis (Global and Planetary Change, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

Review: Artisanal Gold Mining in Africa—Environmental Pollution and Human Health Implications - Maureene Auma Ondayo; Michael J. Watts; Clive J. Mitchell; David C. P. King; Odipo Osano (Exposure and Health, 2024)
About nine million Artisanal and Small-scale Gold Mining (ASGM) workers in Africa and people living near ASGM activities are highly exposed to geogenic and anthropogenic potentially toxic elements (PTEs). Despite the hazards and risks posed by ASGM being well characterized, coordinated multidisciplinary environmental characterization with combined public health studies are limited, with often piecemeal and snapshot studies reported, as highlighted by this review. Furthermore, studies are often not connected with efforts to minimize hazards holistically. Given this, we systematically reviewed the scientific literature on human health hazards associated with ASGM in Africa through Google Scholar, Science Direct, and Pubmed databases. One hundred and seventy-three peer-reviewed papers published between 1996 and June 2023 from 30 African countries were identified. Toxicological environmental hazards were reported in 102 peer-reviewed papers, notably As, Cd, CN, Cr, Hg, Pb, respirable SiO 2 -laden dust, and radionuclides. Exposure to PTEs in human biomonitoring matrices and associated health impacts were documented in 71 papers. Hg was the most reported hazard. Gaps in research robustness, regulation and policy framework, technology, risk detection, surveillance, and management were found. Despite international and in-country mitigation efforts, ASGM-related hazards in Africa are worsening. This review paper highlights the need for coordinated action and multidisciplinary collaborative research to connect dispersed isolated studies to better characterize the associated disease burden associated with ASGM in Africa and sustainably maximize the wider benefits of ASGM whilst protecting public health and the environment.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Water mass influence on spatial and seasonal distributions of diatoms, dinoflagellates and coccolithophores in the western Barents Sea - Qingshan Luan; Elaine Mitchell; Sian F. Henley; Andrew C. M. Orkney; Heather A. Bouman; Judith S. Braun; Alex J. Poulton; Keith Davidson (Polar Biology, 2024)
Arctic phytoplankton are highly sensitive to seawater physical and chemical conditions, especially in the context of rapid climate change and sea ice loss. We studied the spatial and seasonal distributions of diatoms, dinoflagellates and coccolithophores, and clarified their associations with light, temperature and nutrients in the western Barents Sea in late summer 2017, and winter, spring and early summer 2018. Diatoms, composed mainly of Chaetoceros , Fragilariopsis and Thalassiosira , bloomed in spring at the southern border of the marginal ice zone with mean abundance of 1.1 × 10 6 cells L −1 and biomass of 119.5 µg C L −1 , and were observed to follow the retreat of sea ice in the Arctic water to the north at the shelf break near Nansen Basin, contributing to the progression of the summer situation. Dinoflagellates flourished in surface waters south of Svalbard in summer, with maxima of 2.2 × 10 5 cells L −1 and 78.2 µg C L −1 . High abundances and calcite mass of coccolithophores were detected in the southern Barents Sea and southwest of Svalbard in summer, with maxima of 3.3 × 10 5 cells L −1 and 4.7 µg C L −1 . Two distinct phytoplankton assemblages, closely linked with Atlantic water and Arctic water, were geographically separated by the Polar Front in two summers, with a percent similarity below 11.9%, suggesting great influence of the two water masses on large-scale distributions of phytoplankton. Redundancy analysis revealed that temperature was one of the most important factors in shaping the seasonal distributions of diatoms, while irradiance showed positive correlation with dominant dinoflagellates of each season. From the perspectives of phytoplankton composition and carbon biomass, our findings highlight the governing effect of physical seawater conditions on driving seasonal patterns of phytoplankton biogeography, as well as the pivotal role of nutrients in supporting the phytoplankton growing seasons in the western Barents Sea.

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Effective dispersal patterns in prairie plant species across human‐modified landscapes - Elizabeth C. Hendrickson; Mitchell B. Cruzan (Molecular Ecology, 2024)
Effective dispersal among plant populations is dependent on vector behaviour, landscape features and availability of adequate habitats. To capture landscape feature effects on dispersal, studies must be conducted at scales reflecting single‐generation dispersal events (mesoscale). Many studies are conducted at large scales where genetic differentiation is due to dispersal occurring over multiple generations, making it difficult to interpret the effects of specific landscape features on vector behaviour. Genetic structure at the mesoscale may be determined by ecological and evolutionary processes, such as the consequences of vector behaviour on patterns of gene flow. We used chloroplast haplotypes and nuclear genome SNP surveys to identify landscape features influencing seed and pollen dispersal at a mesoscale within the Rogue River Valley in southern Oregon. We evaluated biotic and abiotic vector behaviour by contrasting two annual species with differing dispersal mechanisms; Achyrachaena mollis (Asteraceae) is a self‐pollinating and anemochoric species, and Plectritis congesta (Caprifoliaceae) is biotically pollinated with barochoric seeds. Using landscape genetics methods, we identified features of the study region that conduct or restrict dispersal. We found chloroplast haplotypes were indicative of historic patterns of gene flow prior to human modification of landscapes. Seed dispersal of A . mollis was best supported by models of isolation by distance, while seed‐driven gene flow of P . congesta was determined by the distribution of preserved natural spaces and quality habitat. Nuclear genetic structure was driven by both pollen and seed dispersal, and both species responded to contemporary landscape changes, such as urban and agricultural conversion, and habitat availability.

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Performance of three techniques for diagnosing equine tapeworm infection - Hailey C. Anderson; Shaelin F. Mitchell; Nichol E. Ripley; Martin K. Nielsen (Veterinary Parasitology, 2024)

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Comment on: “Insights on the tectonic styles of the Red Sea rift using gravity and magnetic data” by Saada et al. (2021) - Neil C. Mitchell; Ian C.F. Stewart (Marine and Petroleum Geology, 2024)

Leaf yield and mineral content of mizuna in response to cut-and-come-again harvest, substrate particle size, and fertilizer formulation in a simulated spaceflight environment - Asmaa H. Morsi; Gioia D. Massa; Robert C. Morrow; Raymond M. Wheeler; Mokhles A. Elsysy; Cary A. Mitchell (Life Sciences in Space Research, 2024)

Towards a combined human-natural system approach in the Northern Red Sea Region: Ecological challenges, sustainable development, and community engagement - Ahmed Eladawy; Neil C. Mitchell; Takashi Nakamura; Momen El-Husseiny; Yuta A. Takagi; Nabil Elhady; Brook Muller; Sara Abdel-Hamid; Asmaa Mohammed; Kazuo Nadaoka; J.P. Walsh (Marine Policy, 2024)

Corrigendum to “Oceanic seismotectonics from regional earthquake recordings: The 4–5°N Mid-Atlantic Ridge” [de Melo, G. W., Mitchell, N. C., Zahradnik, J., Dias, F., & do Nascimento, A. F. (2021). Tectonophysics, 819, 229063]. - G.W.S. de Melo; Neil C. Mitchell; Jiri Zahradnik (Tectonophysics, 2024)

Effects of a high cholesterol diet on chill tolerance are highly context-dependent in Drosophila - Mitchell C. Allen; Marshall W. Ritchie; Mahmoud I. El-Saadi; Heath A. MacMillan (Journal of Thermal Biology, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Metabolomes of bumble bees reared in common garden conditions suggest constitutive differences in energy and toxin metabolism across populations - Ellen C. Keaveny; Mitchell R. Helling; Franco Basile; James P. Strange; Jeffrey D. Lozier; Michael E. Dillon (Journal of Insect Physiology, 2023)

The ocean-continent transition in the Western Central Red Sea - Neil C. Mitchell; Jonas Preine; Oke I. Okwokwo; A.Y. Izzeldin; Nico Augustin; Ian C.F. Stewart (Journal of African Earth Sciences, 2023)

Two new genera and a new species of Anacardiaceae from northern South America - John D. Mitchell; Douglas C. Daly; Laura Calvillo-Canadell; Ricardo O. Perdiz (Brittonia, 2023)

Utilising geochemical data for the identification and characterisation of mineral exploration sample media within cover sequence materials - C. J. Tiddy; S. M. Hill; D. Giles; B. G. van der Hoek; V. J. Normington; R. R. Anand; E. Baudet; K. Custance; R. Hill; A. Johnson; S. McLennan; C. Mitchell; et al. (Australian Journal of Earth Sciences, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Observing ocean ecosystem responses to volcanic ash - K.M. Bisson; S. Gassó; N. Mahowald; S. Wagner; B. Koffman; S.A. Carn; S. Deutsch; E. Gazel; S. Kramer; N. Krotkov; C. Mitchell; M.E. Pritchard; et al. (Remote Sensing of Environment, 2023)

Improving the rigor and utility of botanical toxicity studies: Recommended resources - Deval Patel; Barbara C. Sorkin; Constance A. Mitchell; Michelle R. Embry; Sharline Rina-Kong; Rebecca E. Adams; Emily R. DeTemple; Aalekhya Reddam; Stefan Gafner; Olaf Kelber; Cynthia V. Rider; Hellen Oketch-Rabah; et al. (Regulatory Toxicology and Pharmacology, 2023)

Interactions between parasitism and migration in monarch butterflies - Mitchell J Kendzel; Sonia M Altizer; Jacobus C de Roode (Current Opinion in Insect Science, 2023)

Towards hyperlocal source identification of pollutants in cities by combining mobile measurements with atmospheric modeling - John C. Lin; Ben Fasoli; Logan Mitchell; Ryan Bares; Francesca Hopkins; Tammy M. Thompson; Ramón A. Alvarez (Atmospheric Environment, 2023)

Extraction and Digitization of ECG Signals from Standard Clinical Portable Document Format Files for the Principal Component Analysis of T-wave Morphology - Michal Schäfer; Max B. Mitchell; Caitlin Brateng; D. Dunbar Ivy; Kendall S. Hunter; Dustin B. Nash; Johannes C. von Alvensleben (Cardiovascular Engineering and Technology, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Modelling marine microplastics accumulation zones through freshwater discharge sources: Simulated release from the Onkaparinga River and Torrens River, South Australia - Kyle B. Mitchell; Charles James; Jason Gascooke; Sophie C. Leterme (Marine Pollution Bulletin, 2023)

Trace element, rare earth element and trace carbon compounds in Subglacial Lake Whillans, West Antarctica - Clara Turetta; Elena Barbaro; Mark L. Skidmore; Andrea Gambaro; Alexander B. Michaud; Andrew C. Mitchell; Trista J. Vick-Majors; John C. Priscu; Carlo Barbante (Science of The Total Environment, 2023)

Forces, electric fields and currents at the subsolar martian MPB: MAVEN observations and multifluid MHD simulation - G. Boscoboinik; C. Bertucci; D. Gomez; C. Dong; L. Regoli; C. Mazelle; J. Halekas; J. Espley; C.M. Fowler; D. Mitchell; L. Andersson (Icarus, 2023)

“We’re always an afterthought”- Designing tobacco control campaigns for dissemination with and to LGBTQ +—serving community organizations: a thematic analysis - Shoba Ramanadhan; Meg Salvia; Elaine Hanby; Anna C. Revette; Madison K. Rivard; N. F. N. Scout; Julia Applegate; Bob Gordon; Ana Machado; Mitchell R. Lunn; Juno Obedin-Maliver; Jennifer Potter; et al. (Cancer Causes & Control, 2023)
Purpose Evidence-based health communication campaigns can support tobacco control and address tobacco-related inequities among lesbian, gay, bisexual, transgender, and queer (LGBTQ +) populations. Community organizations focused on LGBTQ + health (e.g., nonprofits, community centers, and community health centers) can be prime channels for delivering evidence-based health communication campaigns. However, it is unclear how to balance the goals of a) designing campaigns to support broad adoption/uptake and b) adaptation addressing the needs of diverse communities and contexts. As part of an effort to support “designing for dissemination,” we explored the key challenges and opportunities staff and leaders of LGBTQ + -serving community organizations encounter when adopting or adapting evidence-based health communication campaigns. Methods A team of researchers and advisory committee members conducted this study, many of whom have lived, research, and/or practice experience with LGBTQ + health. We interviewed 22 staff members and leaders of community organizations serving LGBTQ + populations in the US in early 2021. We used a team-based, reflexive thematic analysis approach. Results The findings highlight the challenges of attempting to use health communication campaigns misaligned with the assets and needs of organizations and community members. The three major themes identified were as follows: (1) available evidence-based health communication campaigns typically do not sufficiently center LGBTQ + communities, (2) negotiation regarding campaign utilization places additional burden on practitioners who have to act as “gatekeepers,” and (3) processes of using health communication campaigns often conflict with organizational efforts to engage community members in adoption and adaptation activities. Conclusions We offer a set of considerations to support collaborative design and dissemination of health communication campaigns to organizations serving LGBTQ + communities: (1) develop campaigns with and for LGBTQ + populations, (2) attend to the broader structural forces impacting campaign recipients, (3) support in-house testing and adaptations, and (4) increase access to granular data for community organizations.

Evolution of immunogenetic components encoding ultralong CDR H3 - Jeannine A. Ott; Christian Mitchell; Morgan Sheppard; Thad C. Deiss; J. M. Cody Horton; Jeremy K. Haakenson; Ruiqi Huang; Abigail R. Kelley; Brian W. Davis; James N. Derr; Vaughn V. Smider; Michael F. Criscitiello (Immunogenetics, 2023)

A geochemically informed leak detection (GILD) model for CO2 injection sites - Jiaan Wang; Wei Xiong; James B. Gardiner; Brandon C. McAdams; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano; Mitchell J. Small (Applied Geochemistry, 2023)

Systemic inflammation and biological aging in the Health and Retirement Study - Helen C. S. Meier; Colter Mitchell; Thomas Karadimas; Jessica D. Faul (GeroScience, 2023)
Chronic, low-level systemic inflammation associated with aging, or inflammaging, is a risk factor for several chronic diseases and mortality. Using data from the Health and Retirement Study, we generated a continuous latent variable for systemic inflammation from seven measured indicators of inflammation and examined associations with another biomarker of biological aging, DNA methylation age acceleration measured by epigenetic clocks, and 4-year mortality ( N = 3,113). We found that greater systemic inflammation was positively associated with DNA methylation age acceleration for 10 of the 13 epigenetic clocks, after adjustment for sociodemographics and chronic disease risk factors. The latent variable for systemic inflammation was associated with 4-year mortality independent of DNA methylation age acceleration and was a better predictor of 4-year mortality than any of the epigenetic clocks examined, as well as mortality risk factors, including obesity and multimorbidity. Inflammaging and DNA methylation age acceleration may represent different biological processes contributing to mortality risk. Leveraging multiple measured inflammation markers to capture inflammaging is important for biology of aging research.

Spatial variation in the association between agricultural activities and bird communities in Canada - Gustavo S. Betini; Egina Malaj; Courtney Donkersteeg; Adam C. Smith; Scott Wilson; Greg W. Mitchell; Robert G. Clark; Christine A. Bishop; Lynne E. Burns; Roslyn Dakin; Christy A. Morrissey; Nancy A. Mahony (Science of The Total Environment, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

Reconciling bathymetric and stratigraphic expressions of submarine channel geometry - W. Hamish Mitchell; Alexander C. Whittaker; Mike Mayall; Lidia Lonergan (Marine Geology, 2023)

91 Horse owners’ perspectives of horse weight management - M. Ross; K. Proudfoot; K. Merkies; M. Mills; I. Elsohaby; J. Mitchell; K. MacMillan; S. McKenna; C. Ritter (Journal of Equine Veterinary Science, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Perverse outcomes from fencing fauna: Loss of antipredator traits in a havened mammal population - Natasha D. Harrison; Ben L. Phillips; Nicola J. Mitchell; Julia C. Wayne; Marika A. Maxwell; Colin G. Ward; Adrian F. Wayne (Biological Conservation, 2023)

The Impact of Sleep-Wake Behaviour on Tennis Match Performance in Junior State Grade Tennis Players - Mitchell Turner; Philipp Beranek; Ian C. Dunican; Travis Cruickshank (Journal of Science in Sport and Exercise, 2023)
Purpose To date, no study has investigated the extent to which sleep-wake behaviour (SWB) influences match performance in junior tennis players. This study aimed to assess the influence of SWB for the week and night before on match performance, particularly match analytics and activity. Methods This study recruited 10 junior state grade tennis players who wore an actigraphy device and completed a sleep diary for the week before their match on two separate occasions throughout their competition season. Players wore a global positioning system device to track their movement during matches, and an experienced tennis coach recorded players' match analytics. Results This study showed that the sleep fragmentation index was significantly lower the week before matches in females who had won than those who had lost. Additionally, the sleep fragmentation index was significantly lower the night before a given match than the week before. Only sleep fragmentation index and sleep latency significantly influenced match performance in junior tennis players. The percentage of second serves points won differed between match wins and losses for male players, while winners and forced errors differed for female players. Conclusion These findings provide a detailed profile of tennis match play in junior state grade players. Despite individual differences, reduced restlessness the night before a match coincides with increased match performance.

Using the three horizons approach to explore pathways towards positive futures for agricultural landscapes with rich biodiversity - Tamara Schaal; Michael Mitchell; Ben C. Scheele; Paul Ryan; Jan Hanspach (Sustainability Science, 2023)
In light of the global challenges of the Anthropocene, including biodiversity loss, there are increasing calls for positive, inspirational futures to motivate action and help steer away from current, largely unsustainable trajectories. The three horizons framework is an approach in future studies that engages with normative futures and helps develop pathways towards them. However, this approach has not been applied to explore opportunities for biodiversity conservation with farming communities. We developed a template to apply the three horizons framework in combination with storytelling to explore positive futures for agricultural landscapes with rich biodiversity. We then applied this method over two workshops with a rural community in a farming landscape of south-eastern Australia facing typical contemporary challenges of an ageing population, climate change, biodiversity loss and global market uncertainty. In the workshops, six pathways for change were developed. We unpack these narratives of change to contrast problem framings, future aspirations and mechanisms of change and discuss implications for conservation. We discuss our approach to integrating diverse perspectives and values, creating actionable knowledge and highlight the role of governance and policy to support individual and collective agency. We conclude that the three horizons approach has the potential to create actionable knowledge through locally meaningful narratives of change, and thus influence priorities and empower local action. For lasting on-ground change, leadership and effective cross-scale governance is required.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Experimental and Numerical Investigation into the Fracture Patterns Induced by Blast-Loading Under Unconfined and Confined Conditions - T. R. Mitchell; Z. Wang; M. Araos; C. R. Leonardi; P. R. Gefken; I. A. Onederra (Rock Mechanics and Rock Engineering, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

A redesign of the toothpaste tube using green QFD II for improved usability and sustainability - Danielle S. Angtuaco; Nathan Mitchell A. Barria; Joshua Matthew C. Lee; Jazmin C. Tangsoc; Anthony Shun Fung Chiu; Jose Edgar Mutuc (Journal of Cleaner Production, 2023)

Methyl methacrylate thermal decomposition: Modeling and laser spectroscopy of species time-histories behind reflected shock waves - Isabelle C. Sanders; Nicholas M. Kuenning; Nicolas Q. Minesi; Daniel I. Pineda; R. Mitchell Spearrin (Fuel, 2023)

Direct and indirect effects of agricultural land cover on avian biodiversity in eastern Canada - Michelle Rabbetts; Lenore Fahrig; Greg W. Mitchell; Kevin C. Hannah; Sara J. Collins; Scott Wilson (Biodiversity and Conservation, 2023)
Agriculture is one of the largest threats to global biodiversity. However, most studies have focused only on the direct effects of agriculture on biodiversity, and few have addressed the indirect effects, potentially over or under-estimating the overall impacts of agriculture on biodiversity. The indirect effect is the response not to the agricultural cover types or operations per se , but instead, to the way that agriculture influences the extent and configuration of different types of natural land cover in the landscape. We used structural equation modelling (SEM) to evaluate the direct, indirect, and total effects of agriculture on species richness of three bird guilds: forest birds, shrub-edge birds, and open country birds. We found that forest bird richness was driven by the negative indirect effect of cropland via forest loss. Shrub-edge and open country bird richness increased with the amount of agriculture land covers; however, importantly, we found negative indirect effects of agriculture on both guilds via a reduction in more natural land covers. This latter result highlights how we would have over-estimated the positive effects of agriculture on shrub-edge and open country bird richness had we not measured both direct and indirect effects (i.e., the total effect size is less than the direct effect size). Overall, our results suggest that a bird-friendly agricultural landscape in our region would have forest that is configured to maximize forest edge, and a high proportion of perennial forage within the agricultural portion of the landscape.

Mapping connectivity and conservation opportunity on agricultural lands across the conterminous United States - Justin P. Suraci; Caitlin E. Littlefield; Charlie C. Nicholson; Mitchell C. Hunter; Ann Sorensen; Brett G. Dickson (Biological Conservation, 2023)

Quantifying the Permeability Enhancement from Blast-Induced Microfractures in Porphyry Rocks Using a Cumulant Lattice Boltzmann Method - T. R. Mitchell; A. Roslin; Ł. Łaniewski-Wołłk; I. Onederra; C. R. Leonardi (Transport in Porous Media, 2023)
The permeability of rocks is important in a range of geoscientific applications, including $$\hbox {CO}_{2}$$ CO 2 sequestration, geothermal energy extraction, and in situ mineral recovery. This work presents an investigation of the change in permeability in porphyry rock samples due to blast-induced fracturing. Two samples were analysed before and after exposure to stress waves induced by the detonation of an explosive charge. Micro-computed tomography was used to image the interior of the samples at a pixel resolution of $$10.3\,μ m$$ 10.3 μ m . The images were segmented into void, matrix, and grain to help quantify the differences in the rock samples. Following this, they were binarised as void or solid and the cumulant lattice Boltzmann method (LBM) was applied to simulate the flow of fluid through the connected void space. A correction required with the use of inlet and outlet reservoirs in computational permeability assessment was also proposed. Interrogation of the steady-state flow field allowed the pre- and post-loading permeability to be extracted. Conclusions were then drawn as to the effectiveness of blasting for enhancing fluid accessibility via the generation of microfractures in the rock matrix within the vicinity of a detonated charge. This paper makes contributions in three fundamental areas relating to the numerical assessment of permeability and the enhancement of fluid accessibility in low-porosity rocks. Firstly, a correction factor was proposed to account for the reservoirs commonly imposed on digitised rock samples when investigating sample permeability through numerical methods. Secondly, it validates the benefits of the LBM in handling complex geometries that would be intractable with conventional computational fluid dynamics methods that require body-fitted meshing. This is done with a novel implementation of the cumulant LBM in the open-source TCLB code. Finally, the improvement in fluid accessibility in low-permeability rock samples was shown through the assessment of multiple regions within two blasted samples. It was found that the blast-induced loading can generate extended microfractures that results in multiple orders of magnitude of permeability enhancement if the target rock possesses existing weaknesses and/or mineralisation.

Minimal adaptation of the molecular regulators of mitochondrial dynamics in response to unilateral limb immobilisation and retraining in middle-aged men - Chantal A. Pileggi; Christopher P. Hedges; Randall F. D’Souza; Brenan R. Durainayagam; Nina Zeng; Vandre C. Figueiredo; Anthony J. R. Hickey; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2023)

Multilevel repeatability shows selection may act on both personality and predictability, but neither is state dependent - T.O. Cornwell; D.J. Mitchell; C. Beckmann; A. Joynson; P.A. Biro (Animal Behaviour, 2023)

Development of an enzyme-linked immunosorbent assay for the diagnosis of feline tuberculosis - Jordan L. Mitchell; Chris Wilson; Janet E. Alexander; Shelley G. Rhodes; Danièlle A. Gunn-Moore; Jayne C. Hope (Veterinary Immunology and Immunopathology, 2023)

Innovation in Resident Core Oncology Education: Switching from an Inpatient Ward Rotation to a Hybrid Model of Inpatient Consultations and Outpatient Clinics - Jennifer M. King; Reem Akel; Antoine N. Saliba; Cynthia Wei; Bilal Anouti; Naveen Manchanda; Noelle C. Sinex; Sara Jo Grethlein; Mitchell Goldman (Journal of Cancer Education, 2022)

Lions and brown bears colonized North America in multiple synchronous waves of dispersal across the Bering Land Bridge - Alexander T. Salis; Sarah C. E. Bray; Michael S. Y. Lee; Holly Heiniger; Ross Barnett; James A. Burns; Vladimir Doronichev; Daryl Fedje; Liubov Golovanova; C. Richard Harington; Bryan Hockett; Pavel Kosintsev; et al. (Molecular Ecology, 2022)
The Bering Land Bridge connecting North America and Eurasia was periodically exposed and inundated by oscillating sea levels during the Pleistocene glacial cycles. This land connection allowed the intermittent dispersal of animals, including humans, between Western Beringia (far northeast Asia) and Eastern Beringia (northwest North America), changing the faunal community composition of both continents. The Pleistocene glacial cycles also had profound impacts on temperature, precipitation and vegetation, impacting faunal community structure and demography. While these palaeoenvironmental impacts have been studied in many large herbivores from Beringia (e.g., bison, mammoths, horses), the Pleistocene population dynamics of the diverse guild of carnivorans present in the region are less well understood, due to their lower abundances. In this study, we analyse mitochondrial genome data from ancient brown bears ( Ursus arctos ; n = 103) and lions ( Panthera spp.; n = 39), two megafaunal carnivorans that dispersed into North America during the Pleistocene. Our results reveal striking synchronicity in the population dynamics of Beringian lions and brown bears, with multiple waves of dispersal across the Bering Land Bridge coinciding with glacial periods of low sea levels, as well as synchronous local extinctions in Eastern Beringia during Marine Isotope Stage 3. The evolutionary histories of these two taxa underline the crucial biogeographical role of the Bering Land Bridge in the distribution, turnover and maintenance of megafaunal populations in North America.

Prediction of a conserved pheromone receptor lineage from antennal transcriptomes of the pine sawyer genus Monochamus (Coleoptera: Cerambycidae) - Robert F. Mitchell; Daniel Doucet; Susan Bowman; Marc C. Bouwer; Jeremy D. Allison (Journal of Comparative Physiology A, 2022)

The distribution of mycosporine-like amino acids in phytoplankton across a Southern Ocean transect - Elliot L. Weiss; Mattias Rolf Cape; B. Jack Pan; Maria Vernet; Chase C. James; Tim J. Smyth; Sun-Yong Ha; José L. Iriarte; B. Greg Mitchell (Frontiers in Marine Science, 2022)
Interactions between phytoplankton and ultraviolet radiation (UVR: 280 – 400 nm) are undergoing changes dictated by variability in ocean temperature, the depth of mixed layers, nutrient availability, and the thickness of the ozone layer. There are a variety of mechanisms for phytoplankton to cope with UVR stress, one of the most prevalent being the presence of mycosporine-like amino acids (MAAs). Despite the importance of these molecules to phytoplankton fitness under UVR stress, knowledge of the diversity and distribution of these molecules in the world’s oceans is relatively limited. Here, the composition and distribution of MAAs in phytoplankton were examined in a transect across the Southern Ocean, crossing multiple fronts, from eastern New Zealand to the West Antarctic Peninsula in March and April of 2018. The highest concentration of MAAs (> 0.2 μg/L) was found between 50 and 60°S, as well as along a longitudinal gradient between 137.47 and 144.78°W. A strong correlation was found between a model of the preceding month’s UVR dosage experienced in the mixed layer and the ratio of MAAs to chlorophyll-a across the transect, indicating a relationship between the integrated history of light exposure and phytoplankton physiology. Haptophytes accounted for the majority of biomass north of the polar front (PF) and were strongly correlated with a diversity of MAAs. South of the PF a transition to a community dominated by diatoms was observed, with community composition changes strongly correlated to porphyra-334 concentrations. The data presented here provide a baseline for MAA abundance and association with specific phytoplankton taxa across the Southern Ocean amid a changing climate.

Effects of early-life experience on innovation and problem-solving in captive coyotes - Andrew C. Garcia; Mitchell A. Parsons; Julie K. Young (Behavioral Ecology and Sociobiology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Natural and anthropogenic controls on lake water‐level decline and evaporation‐to‐inflow ratio in the conterminous United States - C. Emi Fergus; J. Renée Brooks; Philip R. Kaufmann; Amina I. Pollard; Richard Mitchell; G. John Geldhof; Ryan A. Hill; Steven G. Paulsen; Paul Ringold; Marc Weber (Limnology and Oceanography, 2022)
Lake water levels are integral to lake function, but hydrologic changes from land and water management may alter lake fluctuations beyond natural ranges. We constructed a conceptual model of multifaceted drivers of lake water levels and evaporation‐to‐inflow ratio (Evap : Inflow). Using a structural equation modeling framework, we tested our model on (1) a national subset of lakes in the conterminous United States with minimal water management to describe natural drivers of lake hydrology and (2) five ecoregional subsets of lakes to explore regional variation in water management effects. Our model fits the national and ecoregional datasets and explained up to 47% of variation in Evap : Inflow, 38% of vertical water level decline, and 79% of horizontal water level decline (littoral exposure). For lakes with minimal water management, Evap : Inflow was related to lake depth ( β = −0.31) and surface inflow ( β = −0.44); vertical decline was related to annual climate (e.g., precipitation β = −0.18) and water management ( β = −0.21); and horizontal decline was largely related to vertical decline ( β = 0.73) and lake morphometry (e.g., depth β = −0.18). Anthropogenic effects varied by ecoregion and likely reflect differences in regional water management and climate. In the West, water management indicators were related to greater vertical decline ( β = 0.38), whereas in the Midwest, these indicators were related to more stable and full lake levels ( β = −0.22) even during drought conditions. National analyses show how human water use interacts with regional climate resulting in contrasting impacts to lake hydrologic variation in the United States.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Water quality inequality: a non-targeted hotspot analysis for ambient water quality injustices - Justine A. Neville; Jaclyn Guz; Helen M. Rosko; Mitchell C. Owens (Hydrological Sciences Journal, 2022)

Genomic evidence of an ancient inland temperate rainforest in the Pacific Northwest of North America - Megan Ruffley; Megan L. Smith; Anahí Espíndola; Daniel F. Turck; Niels Mitchell; Bryan Carstens; Jack Sullivan; David C. Tank (Molecular Ecology, 2022)
The disjunct temperate rainforests of the Pacific Northwest of North America (PNW) are characterized by late‐successional dominant tree species Thuja plicata (western redcedar) and Tsuga heterophylla (western hemlock). The demographic histories of these species, along with the PNW rainforest ecosystem in its entirety, have been heavily impacted by geological and climatic changes the PNW has experienced over the last 5 million years, including mountain orogeny and repeated Pleistocene glaciations. These environmental events have ultimately shaped the history of these species, with inland populations potentially being extirpated during the Pleistocene glaciations. Here, we collect genomic data for both species across their ranges to test multiple demographic models, each reflecting a different phylogeographical hypothesis on how the ecosystem‐dominating species may have responded to dramatic climatic change. Our results indicate that inland and coastal populations in both species diverged ~2.5 million years ago in the early Pleistocene and experienced decreases in population size during glacial cycles, with subsequent population expansion. Importantly, we found evidence for gene flow between coastal and inland populations during the mid‐Holocene. It is likely that intermittent migration in these species during this time has prevented allopatric speciation via genetic drift alone. In conclusion, our results from combining genomic data and demographic inference procedures establish that populations of the ecosystem dominants Thuja plicata and Tsuga heterophylla persisted in refugia located in both the coastal and inland regions of the PNW throughout the Pleistocene, with populations expanding and contracting in response to glacial cycles with occasional gene flow.

Sexual assault and white matter hyperintensities among midlife women - Rebecca C. Thurston; Karen P. Jakubowski; Minjie Wu; Howard J. Aizenstein; Yuefang Chang; Carol A. Derby; Karestan C. Koenen; Emma Barinas-Mitchell; Pauline M. Maki (Brain Imaging and Behavior, 2022)

Description of two new bird species from the Meratus Mountains of southeast Borneo, Indonesia - Mohammad Irham; Tri Haryoko; Subir B. Shakya; Simon L. Mitchell; Ryan C. Burner; Carlos Bocos; James A. Eaton; Frank E. Rheindt; Suparno Suparno; Frederick H. Sheldon; Dewi M. Prawiradilaga (Journal of Ornithology, 2022)

Methionol, a Sulfur-Containing Pheromone Component from the North American Cerambycid Beetle Knulliana cincta cincta - Marlin E. Rice; Lawrence M. Hanks; Sean Halloran; Judith A. Mongold-Diers; Anna C. Grommes; Robert F. Mitchell; Ann M. Ray; Jocelyn G. Millar (Journal of Chemical Ecology, 2022)

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Crustal storage and ascent history of the Mt. Shasta primitive magnesian andesite: implications for arc magma crustal flux rates - Mitchell Phillips; C. B. Till (Contributions to Mineralogy and Petrology, 2022)

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Sediment Transport and Morphological Response to Nearshore Nourishment Projects on Wave-Dominated Coasts - Cody L. Johnson; Brian C. McFall; Douglas R. Krafft; Mitchell E. Brown (Journal of Marine Science and Engineering, 2021)
Nearshore nourishments are constructed for shoreline protection from waves, to provide sediment nourishment to the beach profile, and to beneficially use dredged sediment from navigation channel maintenance. However, it is poorly understood how placement morphology and depth influence nearshore processes operated on wave-dominated coasts. This study investigates the wave fields, sediment transport, and morphological response to three common nearshore nourishment shapes, nearshore berm (elongated bar), undulated nearshore berm, and small discrete mounds, with numerical experiments utilizing the Coastal Modeling System. The nourishments are placed in depths between 3 m and 7 m with a volume of approximately 100,000 m3 and between 400 m and 1000 m in alongshore length. Numerical experiments are carried out in three distinct coastal settings with representative wave climates and geomorphology. Simulation results indicate that shallower, more continuous berms attenuate the most wave energy, while deeper, more diffuse placements retain more sediment. Results from this study improve the understanding of nearshore nourishment shapes and can support decision makers identifying the most appropriate construction technique for future nearshore nourishment projects.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Bathymetric Data Requirements for Operational Coastal Erosion Forecasting Using XBeach - Nashwan Matheen; Mitchell D. Harley; Ian L. Turner; Kristen D. Splinter; Joshua A. Simmons; Mandi C. Thran (Journal of Marine Science and Engineering, 2021)
There is an increasing interest in the broad-scale implementation of coastal erosion early warning systems (EWS) with the goal of enhancing community preparedness to extreme coastal storm wave events. These emerging systems typically rely on process-based models to predict the storm-induced morphological change. A key challenge with incorporating these models in EWSs is the need for up-to-date nearshore and surf zone bathymetry data, which is difficult to measure routinely, but potentially important for accurate erosion forecasting. This study evaluates the degree to which up-to-date bathymetry is required for accurate coastal erosion predictions using the morphodynamic model XBeach and, subsequently, whether a range of “representative” and/or “synthetic” bathymetries can be used for the bottom boundary, when a survey of the immediate pre-storm bathymetry is not available. Twelve storm events at two contrasting sites were modelled using six different bathymetry scenarios, including the expected “best case” bathymetry surveyed immediately pre-storm. These results indicate that alternative bathymetries can be used to obtain sub-aerial erosion predictions that are similar (and in some cases better) than those resulting from the use of an immediately pre-storm surveyed bathymetry, provided that rigorous model calibration is undertaken prior. This generalized finding is attributed to specific parametrizations in the XBeach model structure that are optimized during the calibration process to match the particular bottom boundary condition used. This study provides practical guidance for the selection of suitable nearshore bathymetry for use in operational coastal erosion EWSs.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.

Heavy rare-earth element and Y partitioning between monazite and garnet in aluminous granulites - Shujuan Jiao; Noreen J. Evans; Ross N. Mitchell; Ian C. W. Fitzsimons; Jinghui Guo (Contributions to Mineralogy and Petrology, 2021)

Motor network connectivity predicts neuroplastic response following theta burst stimulation in healthy adults - Brenton Hordacre; Mitchell R. Goldsworthy; Lynton Graetz; Michael C. Ridding (Brain Structure and Function, 2021)

Chemokine-Induced PBMC and Subsequent MSC Migration Toward Decellularized Heart Valve Tissue - Mitchell C. VeDepo; Kyra Flores; Jeffrey G. Jacot (Cardiovascular Engineering and Technology, 2021)

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

Neuropsychiatric Symptoms as a Reliable Phenomenology of Cerebellar Ataxia - Sharif I. Kronemer; Mitchell B. Slapik; Jessica R. Pietrowski; Michael J. Margron; Owen P. Morgan; Catherine C. Bakker; Liana S. Rosenthal; Chiadi U. Onyike; Cherie L. Marvel (The Cerebellum, 2021)

Plasma anti-CD4 IgG is associated with brain abnormalities in people with HIV on antiretroviral therapy - Scott Bowler; Brooks I. Mitchell; Kalpana J. Kallianpur; Dominic Chow; Wei Jiang; Cecilia M. Shikuma; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2021)

Dependence on a human structure influences the extinction of a non-native lizard population after a major environmental change - Daniel A. Warner; Joshua M. Hall; Amélie Fargevieille; Austin C. Hulbert; Sarin Tiatragul; Jenna E. Pruett; Timothy S. Mitchell (Biological Invasions, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

The Role of Alpha Power in the Suppression of Anticipated Distractors During Verbal Working Memory - Sabrina Sghirripa; Lynton Graetz; Ashley Merkin; Nigel C Rogasch; Michael C Ridding; John G Semmler; Mitchell R Goldsworthy (Brain Topography, 2021)

Coastal carbon cycle changes following mangrove loss - James Z. Sippo; Christian J. Sanders; Isaac R. Santos; Luke C. Jeffrey; Mitchell Call; Yota Harada; Kylie Maguire; Dylan Brown; Stephen R. Conrad; Damien T. Maher (Limnology and Oceanography, 2020)
Global mangrove loss is occurring from deforestation and extreme climatic events, but changes to the coastal carbon cycle following mangrove mortality and/or loss are not well understood. In 2015/2016, a massive climate‐driven mangrove dieback event occurred over ~ 1000 km of Australian coastline. To assess carbon loss following mortality, carbon fluxes in adjacent living and dead forest areas were compared 8 and 20 months postforest dieback. Dead areas experienced an increase in soil CO 2 efflux by ~ 189%, and a decrease in oceanic dissolved inorganic carbon (DIC) outwelling of ~ 50% relative to living areas. DIC outwelling (predominantly carbonate alkalinity) and soil CO 2 efflux accounted for 81% and 16% of losses from the living forest, in comparison to 51% and 47%, respectively, from the dead forest. The dieback drove a shift from a dominance of oceanic carbon outwelling to increased atmospheric CO 2 emissions and decreased alkalinity exports. This shift was likely driven by increased oxygen sediment permeation and the loss of mangrove net primary productivity. Combining our new observations with literature data, we found a logarithmic relationship between soil carbon loss and time since mangrove loss. Using this relationship, we estimate ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C yr −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60%. Even if no future deforestation occurred, we estimate ongoing carbon losses to the atmosphere and ocean from current global mangrove losses of 27 Tg C over the next 30 yr.

Maleic hydrazide elicits global transcriptomic changes in chemically topped tobacco to influence shoot bud development - Sanjay K. Singh; Mitchell D. Richmond; Robert C. Pearce; William A. Bailey; Xin Hou; Sitakanta Pattanaik; Ling Yuan (Planta, 2020)

Evaluation of implementation of risk management guidelines for carriers of pathogenic variants in mismatch repair genes: a nationwide audit of familial cancer clinics - B. Meiser; R. Kaur; J. Kirk; A. Morrow; M. Peate; W. K. T. Wong; E. McPike; E. Cops; C. Dowson; R. Austin; M. Fine; L. Thrupp; et al. (Familial Cancer, 2020)

Response to Letter to the Editor: Are five 60-min sessions of isothermic heat acclimation sufficient to elicit beneficial physiological adaptations? - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)

Tree planting in organic soils does not result in net carbon sequestration on decadal timescales - Nina L. Friggens; Alison J. Hester; Ruth J. Mitchell; Thomas C. Parker; Jens‐Arne Subke; Philip A. Wookey (Global Change Biology, 2020)
Tree planting is increasingly being proposed as a strategy to combat climate change through carbon (C) sequestration in tree biomass. However, total ecosystem C storage that includes soil organic C (SOC) must be considered to determine whether planting trees for climate change mitigation results in increased C storage. We show that planting two native tree species ( Betula pubescens and Pinus sylvestris ), of widespread Eurasian distribution, onto heather ( Calluna vulgaris ) moorland with podzolic and peaty podzolic soils in Scotland, did not lead to an increase in net ecosystem C stock 12 or 39 years after planting. Plots with trees had greater soil respiration and lower SOC in organic soil horizons than heather control plots. The decline in SOC cancelled out the increment in C stocks in tree biomass on decadal timescales. At all four experimental sites sampled, there was no net gain in ecosystem C stocks 12–39 years after afforestation—indeed we found a net ecosystem C loss in one of four sites with deciduous B. pubescens stands; no net gain in ecosystem C at three sites planted with B. pubescens ; and no net gain at additional stands of P. sylvestris . We hypothesize that altered mycorrhizal communities and autotrophic C inputs have led to positive ‘priming’ of soil organic matter, resulting in SOC loss, constraining the benefits of tree planting for ecosystem C sequestration. The results are of direct relevance to current policies, which promote tree planting on the assumption that this will increase net ecosystem C storage and contribute to climate change mitigation. Ecosystem‐level biogeochemistry and C fluxes must be better quantified and understood before we can be assured that large‐scale tree planting in regions with considerable pre‐existing SOC stocks will have the intended policy and climate change mitigation outcomes.

Calibration of a common shortwave multispectral camera system for quantitative agricultural applications - J. Burdette Barker; Wayne E. Woldt; Brian D. Wardlow; Christopher M. U. Neale; Mitchell S. Maguire; Bryan C. Leavitt; Derek M. Heeren (Precision Agriculture, 2020)

MitoQ and CoQ10 supplementation mildly suppresses skeletal muscle mitochondrial hydrogen peroxide levels without impacting mitochondrial function in middle-aged men - Toan Pham; Caitlin L. MacRae; Sophie C. Broome; Randall F. D’souza; Ravi Narang; Hsiang W. Wang; Trevor A. Mori; Anthony J. R. Hickey; Cameron J. Mitchell; Troy L. Merry (European Journal of Applied Physiology, 2020)

Evaluation of Structured and Unstructured Models for Application in Operational Ocean Forecasting in Nearshore Waters - Shannon Nudds; Youyu Lu; Simon Higginson; Susan P. Haigh; Jean-Philippe Paquin; Mitchell O’Flaherty-Sproul; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Gregory C. Smith; Natacha B. Bernier; Phillip MacAulay; et al. (Journal of Marine Science and Engineering, 2020)
The oceanography sub-initiative of Canada’s Oceans Protection Plan was tasked to develop high-resolution nearshore ocean models for enhanced marine safety and emergency response, fitting into the multi-scale, multi-level nested operational ocean forecasting systems. For decision making on eventual 24/7 operational support, two ocean models (a structured grid model, NEMO (Nucleus for European Modelling of the Ocean); and an unstructured grid model, FVCOM (Finite Volume Coastal Ocean Model), were evaluated. The evaluation process includes the selection of the study area, the requirements for model setup, and the evaluation metrics. The chosen study area, Saint John Harbour in the Bay of Fundy, features strong tides, significant river runoff and a narrow tidal-river channel. Both models were configured with the same sources of bathymetry and forcing data. FVCOM achieved 50-100 m horizontal resolution in the inner harbour and included wetting/drying. NEMO achieved 100 m resolution in the harbour with a three-level one-way nesting configuration. Statistical metrics showed that one-year simulations with both models achieved comparable accuracies against the observed tidal and non-tidal water levels and currents, temperature and salinity, and the trajectories of surface drifters, but the computational cost of FVCOM was significantly less than that of NEMO.

Use of human-made structures facilitates persistence of a non-native ectotherm - Austin C. Hulbert; Joshua M. Hall; Timothy S. Mitchell; Daniel A. Warner (Biological Invasions, 2020)

Photosynthetic properties of juvenile Prumnopitys taxifolia (Podocarpaceae), a divaricate and heteroblastic conifer - Antigone E. T. Mitchell; Barry A. Logan; Jaret S. Reblin; Kevin C. Burns; Kevin S. Gould (New Zealand Journal of Botany, 2020)
The crowns of juvenile Prumnopitys taxifolia (D. Don) de Laub. are comprised of thin, interlaced, wiry stems branching at wide angles and bearing sparse, scale‐like, clasping leaves (‘divaricating’ shoots) that generally surround stems bearing oblong, compressed leaves (‘leafy’ shoots). As development proceeds, non‐divaricating branches of the mature tree form exclusively; thus, P. taxifolia is profoundly heteroblastic. Divaricating stems of juvenile P. taxifolia are brown in appearance and possess very low leaf areas. As such, one might assume that they perform little photosynthesis, returning very little fixed carbon in return for the cost of their construction, and thus represent a significant cost to the overall carbon economy of the whole plant. We examined the hypothesis that divaricating P. taxifolia stems are photosynthetically active, thus mitigating this perceived cost. We found that divaricating shoots, though brown in colouration, possessed chlorophyll contents and capacities for photosynthetic O 2 evolution on par with those of leafy shoots. Interestingly, measured rates of CO 2 assimilation in divaricating shoots were only ∼ half those of leafy shoots. This difference may be explained by the assimilation of internal CO 2 (i.e. CO 2 generated by or transported through divaricating stems), which is not measured by traditional gas exchange methods. We conclude that analyses of the costs associated with the evolution of divarication or heteroblasty in P. taxifolia should take into account the photosynthetic activity of divaricating stems. A survey of the photosynthetic properties of divaricating stems of other species might contribute to our understanding of the origins and functional significance of this fascinating phenomenon.

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Dietary Ecology of the Nigeria–Cameroon Chimpanzee (Pan troglodytes ellioti) - Ekwoge E. Abwe; Bethan J. Morgan; Roger Doudja; Fabrice Kentatchime; Flaubert Mba; Alvine Dadjo; Dana M. Venditti; Matthew W. Mitchell; Bernard Fosso; Albert Mounga; Roger C. Fotso; Mary Katherine Gonder (International Journal of Primatology, 2020)

Didymosphenia geminata blooms are not exclusively driven by low phosphorus under experimental conditions - Derek C. West; Jared A. Balik; Mitchell Owens; Brad W. Taylor (Hydrobiologia, 2020)

Short-term isothermic heat acclimation elicits beneficial adaptations but medium-term elicits a more complete adaptation - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)
Purpose To investigate the effects of 60 min daily, short-term (STHA) and medium-term (MTHA) isothermic heat acclimation (HA) on the physiological and perceptual responses to exercise heat stress. Methods Sixteen, ultra-endurance runners (female = 3) visited the laboratory on 13 occasions. A 45 min sub-maximal (40% W max ) cycling heat stress test (HST) was completed in the heat (40 °C, 50% relative humidity) on the first (HST PRE ), seventh (HST STHA ) and thirteenth (HST MTHA ) visit. Participants completed 5 consecutive days of a 60 min isothermic HA protocol (target T re 38.5 °C) between HST PRE and HST STHA and 5 more between HST STHA and HST MTHA . Heart rate (HR), rectal ( T re ), skin ( T sk ) and mean body temperature ( T body ), perceived exertion (RPE), thermal comfort (TC) and sensation (TS) were recorded every 5 min. During HSTs, cortisol was measured pre and post and expired air was collected at 15, 30 and 45 min. Results At rest, T re and T body were lower in HST STHA and HST MTHA compared to HST PRE, but resting HR was not different between trials. Mean exercising T re , T sk , T body , and HR were lower in both HST STHA and HST MTHA compared to HST PRE . There were no differences between HST STHA and HST MTHA . Perceptual measurements were lowered by HA and further reduced during HST MTHA . Conclusion A 60 min a day isothermic STHA was successful at reducing physiological and perceptual strain experienced when exercising in the heat; however, MTHA offered a more complete adaptation.

Ultradian oscillations in brain temperature in sheep: implications for thermoregulatory control? - Andrea Fuller; Robyn S. Hetem; Leith C. R. Meyer; Duncan Mitchell; Shane K. Maloney (Journal of Comparative Physiology B, 2020)

The importance of turtle populations to wetland restoration in the Upper Mississippi Embayment of the Mississippi Alluvial Valley - Max A. Nickerson; Joseph C. Mitchell; Brad M. Glorioso (Wetlands Ecology and Management, 2019)

Non-physiologic Bioreactor Processing Conditions for Heart Valve Tissue Engineering - Mitchell C. VeDepo; Eric E. Buse; Arghya Paul; Gabriel L. Converse; Richard A. Hopkins (Cardiovascular Engineering and Technology, 2019)

S100B and its association with HIV-associated neurocognitive disorders - Nath Limpruttidham; Brooks I. Mitchell; Kalpana J. Kallianpur; Beau K. Nakamoto; Scott A. Souza; Bruce Shiramizu; Lishomwa C. Ndhlovu; Dominic C. Chow; Cecilia M. Shikuma (Journal of NeuroVirology, 2019)

Contrasting scales of local persistence between monsoonal and arid biomes in closely related, low‐dispersal vertebrates - Sally Potter; Ana C. Afonso Silva; Jason G. Bragg; Sarah R. Catalano; Stephen Donnellan; Paul Doughty; Mitchell L. Scott; Craig Moritz (Journal of Biogeography, 2019)
Aim Focussing on pairs of sister species across three genera of scincid lizards, we use genomic evidence to test for larger‐scale, late‐Pleistocene changes in distributions of lizards in the Australian arid zone (AZ) than in the adjacent monsoonal tropics (MT). Location Northern and central Australia. Taxon Scincidae: Squamata. Methods We sequenced ~2000 nuclear exons and one mitochondrial gene across the distributions of species with primarily MT or AZ distributions from three genera of lizards. Using phylogenetic analysis and population structure analyses we identified major phylogeographic lineages and then compared the spatial scale of structuring and tested for recent demographic expansions. Results Two genera in particular, Proablepharus and Morethia , showed deeper and more geographically localized phylogeographic diversity in the MT than the AZ. In the MT, localized diversity was prevalent in the relatively mesic regions. By contrast, the AZ was characterized by widespread and often genetically uniform lineages and a higher proportion of these had signals of recent population expansion. Main conclusions Consistent with other recent, but mostly less genetically extensive studies, our results point to deeper and more localized diversity in MT compared to AZ. In turn, this suggests higher local persistence in more mesic and topographically diverse biome through the late Quaternary climate fluctuations. For the AZ, geographically extensive range expansions have likely contributed to the low spatial turnover of this exceptionally rich lizard fauna.

Colloid Transport in Porous Media: A Review of Classical Mechanisms and Emerging Topics - Ian L. Molnar; Erica Pensini; Md Abdullah Asad; Chven A. Mitchell; Ludwig C. Nitsche; Laura J. Pyrak-Nolte; Gastón L. Miño; Magdalena M. Krol (Transport in Porous Media, 2019)

Assessing ecosystem service trade-offs and synergies: The need for a more mechanistic approach - Marie C. Dade; Matthew G.E. Mitchell; Clive A. McAlpine; Jonathan R. Rhodes (Ambio, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Deeply conserved susceptibility in a multi‐host, multi‐parasite system - Lisa N. Barrow; Sabrina M. McNew; Nora Mitchell; Spencer C. Galen; Holly L. Lutz; Heather Skeen; Thomas Valqui; Jason D. Weckstein; Christopher C. Witt (Ecology Letters, 2019)
Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection status, we applied Bayesian phylogenetic multilevel models that included a suite of environmental, spatial, temporal, life history and ecological predictors. We found evidence of deeply conserved susceptibility across the avian tree; host phylogeny explained substantial variation in infection status, and results were robust to phylogenetic uncertainty. Our study suggests that susceptibility is governed, in part, by conserved, latent aspects of anti‐parasite defence. This demonstrates the importance of deep phylogeny for understanding present‐day ecological interactions.

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Saliou Niassy; Amanuel Tamiru; James G. C. Hamilton; William D. J. Kirk; Roland Mumm; Cassie Sims; Willem Jan de Kogel; Sunday Ekesi; Nguya K. Maniania; Krishnakumari Bandi; Fraser Mitchell; Sevgan Subramanian (Journal of Chemical Ecology, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Equatorial Pacific gravity lineaments: interpretations with basement topography along seismic reflection lines - Neil C. Mitchell; Huw Davies (Marine Geophysical Research, 2018)

Preparation of polycaprolactone nanoparticles via supercritical carbon dioxide extraction of emulsions - Adejumoke Lara Ajiboye; Vivek Trivedi; John C. Mitchell (Drug Delivery and Translational Research, 2018)

Fruit Morphology and Anatomy of the Spondioid Anacardiaceae - Fabiany Herrera; John D. Mitchell; Susan K. Pell; Margaret E. Collinson; Douglas C. Daly; Steven R. Manchester (The Botanical Review, 2018)

Response of cell-wall composition and RNA-seq transcriptome to methyl-jasmonate in Brachypodium distachyon callus - Lucy S. Hyde; Till K. Pellny; Jackie Freeman; Louise V. Michaelson; Rachael Simister; Simon J. McQueen-Mason; Rowan A. C. Mitchell (Planta, 2018)

Taxonomic and metabolic shifts in the Coorong bacterial metagenome driven by salinity and external inputs - Kelly Newton; Thomas C. Jeffries; Renee J. Smith; Justin R. Seymour; Laurent Seuront; James G. Mitchell (Journal of Oceanology and Limnology, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

Engaging stakeholders in research to address water–energy–food (WEF) nexus challenges - C. Hoolohan; A. Larkin; C. McLachlan; R. Falconer; I. Soutar; J. Suckling; L. Varga; I. Haltas; A. Druckman; D. Lumbroso; M. Scott; D. Gilmour; et al. (Sustainability Science, 2018)

Characterization of isolated liver sinusoidal endothelial cells for liver bioengineering - A. M. Dingle; K. K. Yap; Y-W. Gerrand; C. J. Taylor; E. Keramidaris; Z. Lokmic; A. M. Kong; H. L. Peters; W. A. Morrison; G. M. Mitchell (Angiogenesis, 2018)

Respiratory syncytial virus prophylaxis in cystic fibrosis: the Canadian registry of palivizumab data (2005–2016) - Ian Mitchell; S. K. Wong; B. Paes; M. Ruff; C. Bjornson; A. Li; K. L. Lanctôt (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Interdisciplinary Oncology Education: a National Survey of Trainees and Program Directors in the United States - Adil S. Akthar; Christopher D. Hellekson; Sabha Ganai; Olwen M. Hahn; Ronald J. Maggiore; Ezra E. Cohen; Mitchell C. Posner; Steven J. Chmura; Andrew R. Howard; Daniel W. Golden (Journal of Cancer Education, 2018)

An update in international trends in incidence rates of thyroid cancer, 1973–2007 - Benjamin C. James; Janeil M. Mitchell; Heedo D. Jeon; Nektarios Vasilottos; Raymon H. Grogan; Briseis Aschebrook-Kilfoy (Cancer Causes & Control, 2018)

Challenges and opportunities for managing aquatic mercury pollution in altered landscapes - Heileen Hsu-Kim; Chris S. Eckley; Dario Achá; Xinbin Feng; Cynthia C. Gilmour; Sofi Jonsson; Carl P. J. Mitchell (Ambio, 2018)

Ancient mitochondrial genomes reveal the demographic history and phylogeography of the extinct, enigmatic thylacine ( Thylacinus cynocephalus ) - Lauren C. White; Kieren J. Mitchell; Jeremy J. Austin (Journal of Biogeography, 2018)
Aim The Tasmanian tiger, or thylacine, is an infamous example of a recent human‐mediated extinction. Confined to the island of Tasmania in historical times, thylacines were hunted to extinction c . 3,200 years before present ( bp ). Very little is known about thylacine biology and population history; the cause of the thylacines extirpation from the mainland is still debated and the reasons for its survival in Tasmania into the 20th century are unclear. In this study, we investigate the thylacine's phylogeography and demographic history leading up to their extinction on both the mainland and Tasmania to gain insight into this enigmatic species. Location Southern Australia. Methods We generated 51 new thylacine mitochondrial DNA (mt DNA ) genome sequences from sub‐fossil remains and historical museum specimens, and analysed them to reconstruct the species’ phylogeography and demographic history. Results We found evidence that thylacines had contracted into separate eastern and western populations prior to the Last Glacial Maximum ( c . 25,000 yr bp ), and that the ancient western population was larger and more genetically diverse than the historical Tasmanian population. At the time of European arrival in c . 1800 CE , Tasmanian thylacines had limited mt DNA diversity, possibly resulting from a bottleneck event broadly coincident with an El Niño‐Southern Oscillation ( ENSO ) associated climate event, although we find some indication that the population was expanding during the late Holocene. Main Conclusions The timing of this putative expansion, in concert with a climate event, suggests that climate change had an influence on thylacine population dynamics. Given that ENSO effects are known to have been more severe on mainland Australia, we suggest that climate change, in synergy with other drivers, is likely to have contributed to the thylacine mainland extinction.

Extreme weather‐year sequences have nonadditive effects on environmental nitrogen losses - Javed Iqbal; Magdalena Necpalova; Sotirios V. Archontoulis; Robert P. Anex; Marie Bourguignon; Daryl Herzmann; David C. Mitchell; John E. Sawyer; Qing Zhu; Michael J. Castellano (Global Change Biology, 2018)
The frequency and intensity of extreme weather years, characterized by abnormal precipitation and temperature, are increasing. In isolation, these years have disproportionately large effects on environmental N losses. However, the sequence of extreme weather years (e.g., wet–dry vs. dry–wet) may affect cumulative N losses. We calibrated and validated the DAYCENT ecosystem process model with a comprehensive set of biogeophysical measurements from a corn–soybean rotation managed at three N fertilizer inputs with and without a winter cover crop in Iowa, USA . Our objectives were to determine: (i) how 2‐year sequences of extreme weather affect 2‐year cumulative N losses across the crop rotation, and (ii) if N fertilizer management and the inclusion of a winter cover crop between corn and soybean mitigate the effect of extreme weather on N losses. Using historical weather (1951–2013), we created nine 2‐year scenarios with all possible combinations of the driest (“dry”), wettest (“wet”), and average (“normal”) weather years. We analyzed the effects of these scenarios following several consecutive years of relatively normal weather. Compared with the normal–normal 2‐year weather scenario, 2‐year extreme weather scenarios affected 2‐year cumulative NO 3 − leaching (range: −93 to +290%) more than N 2 O emissions (range: −49 to +18%). The 2‐year weather scenarios had nonadditive effects on N losses: compared with the normal–normal scenario, the dry–wet sequence decreased 2‐year cumulative N 2 O emissions while the wet–dry sequence increased 2‐year cumulative N 2 O emissions. Although dry weather decreased NO 3 − leaching and N 2 O emissions in isolation, 2‐year cumulative N losses from the wet–dry scenario were greater than the dry–wet scenario. Cover crops reduced the effects of extreme weather on NO 3 − leaching but had a lesser effect on N 2 O emissions. As the frequency of extreme weather is expected to increase, these data suggest that the sequence of interannual weather patterns can be used to develop short‐term mitigation strategies that manipulate N fertilizer and crop rotation to maximize crop N uptake while reducing environmental N losses.

Notes on Astronium Jacq. (Anacardiaceae), including a dwarf new species from the Brazilian Shield - John D. Mitchell; Douglas C. Daly (Brittonia, 2017)

Microvascular ultrastructural changes precede cognitive impairment in the murine APPswe/PS1dE9 model of Alzheimer’s disease - Patricia Kelly; Paul Denver; Simon C. Satchell; Maximilian Ackermann; Moritz A. Konerding; Christopher A. Mitchell (Angiogenesis, 2017)

Odorant receptors and antennal lobe morphology offer a new approach to understanding olfaction in the Asian longhorned beetle - Robert F. Mitchell; Loyal P. Hall; Peter F. Reagel; Duane D. McKenna; Thomas C. Baker; John G. Hildebrand (Journal of Comparative Physiology A, 2017)

Using high-resolution LiDAR data to quantify the three-dimensional structure of vegetation in urban green space - Rhiannon J. C. Caynes; Matthew G. E. Mitchell; Dan Sabrina Wu; Kasper Johansen; Jonathan R. Rhodes (Urban Ecosystems, 2016)

Comment on: “The spatial extent of the Deep Western Boundary Current into the Bounty Trough: new evidence from parasound sub-bottom profiling” by Horn and Uenzelmann-Neben - Neil C. Mitchell (Marine Geophysical Research, 2016)

A Multi-laboratory in Vitro Study to Compare Data from Abbreviated and Pharmacopeial Impactor Measurements for Orally Inhaled Products: a Report of the European Aerosol Group (EPAG) - Steven C. Nichols; Jolyon P. Mitchell; Dennis Sandell; Patrik U. Andersson; Manfred Fischer; Markus Howald; Roy Pengilley; Phillip Krüger (AAPS PharmSciTech, 2016)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

Syntrophic associations from hypersaline soda lakes converting organic acids and alcohols to methane at extremely haloalkaline conditions - Dimitry Y. Sorokin; Ben Abbas; Mitchell Geleijnse; Tatjana V. Kolganova; Robbert Kleerebezem; Mark C. M. van Loosdrecht (Environmental Microbiology, 2016)
Summary Until now anaerobic oxidation of VFA at high salt‐pH has been demonstrated only at sulfate‐reducing conditions. Here, we present results of a microbiological investigation of anaerobic conversion of organic acids and alcohols at methanogenic conditions by syntrophic associations enriched from hypersaline soda lakes in Central Asia. Sediment incubation experiments showed active, albeit very slow, methane formation from acetate, propionate, butyrate and C 2 C 4 alcohols at pH 10 and various levels of salinity. Enrichments of syntrophic associations using hydrogenotrophic members of the genus Methanocalculus from soda lakes as partners resulted in several highly enriched cultures converting acetate, propionate, butyrate, benzoate and EtOH to methane. Most syntrophs belonged to Firmicutes , while the propionate‐oxidizer formed a novel lineage within the family Syntrophobacteraceae in the Deltaproteobacteria . The acetate‐oxidizing syntroph was identified as ‘ Ca . Syntrophonatronum acetioxidans’ previously found to oxidize acetate at sulfate‐reducing conditions up to salt‐saturating concentrations. Butyrate and a benzoate‐degrading syntrophs represent novel genus‐level lineages in Syntrophomonadales which are proposed as Candidatus taxons ‘Syntrophobaca’, ‘Syntrophocurvum’ and ‘Syntropholuna’. Overall, despite very slow growth, the results indicated the presence of a functionally competent syntrophic community in hypersaline soda lakes, capable of efficient oxidation of fermentation products to methane at extremely haloalkaline conditions.

Productivity and species richness in longleaf pine woodlands: resource‐disturbance influences across an edaphic gradient - L. K. Kirkman; L. M. Giencke; R. S. Taylor; L. R. Boring; C. L. Staudhammer; R. J. Mitchell (Ecology, 2016)
This study examines the complex feedback mechanisms that regulate a positive relationship between species richness and productivity in a longleaf pine‐wiregrass woodland. Across a natural soil moisture gradient spanning wet‐mesic to xeric conditions, two large scale manipulations over a 10‐yr period were used to determine how limiting resources and fire regulate plant species diversity and productivity at multiple scales. A fully factorial experiment was used to examine productivity and species richness responses to N and water additions. A separate experiment examined standing crop and richness responses to N addition in the presence and absence of fire. Specifically, these manipulations addressed the following questions: (1) How do N and water addition influence annual aboveground net primary productivity of the midstory/overstory and ground cover? (2) How do species richness responses to resource manipulations vary with scale and among functional groups of ground cover species? (3) How does standing crop (including overstory, understory/midstory, and ground cover components) differ between frequently burned and fire excluded plots after a decade without fire? (4) What is the role of fire in regulating species richness responses to N addition? This long‐term study across a soil moisture gradient provides empirical evidence that species richness and productivity in longleaf pine woodlands are strongly regulated by soil moisture. After a decade of treatment, there was an overall species richness decline with N addition, an increase in richness of some functional groups with irrigation, and a substantial decline in species richness with fire exclusion. Changes in species richness in response to treatments were scale‐dependent, occurring primarily at small scales (≤10 m 2 ). Further, with fire exclusion, standing crop of ground cover decreased with N addition and non‐pine understory/midstory increased in wet‐mesic sites. Non‐pine understory/midstory standing crop increased in xeric sites with fire exclusion, but there was no influence of N addition. This study highlights the complexity of interactions among multiple limiting resources, frequent fire, and characteristics of dominant functional groups that link species richness and productivity.

FG-3019, a Human Monoclonal Antibody Recognizing Connective Tissue Growth Factor, is Subject to Target-Mediated Drug Disposition - Mitchell C. Brenner; Wojciech Krzyzanski; James Z. Chou; Pierre E. Signore; Cyra K. Fung; David Guzman; Dongxia Li; Weihua Zhang; David R. Olsen; Viet-Tam L. Nguyen; Carolyn W. Koo; Mark D. Sternlicht; et al. (Pharmaceutical Research, 2016)

Last interglacial (MIS 5e) sea-level determined from a tectonically stable, far-field location, Eyre Peninsula, southern Australia - C. V. Murray-Wallace; A. P. Belperio; A. Dosseto; W. A. Nicholas; C. Mitchell; R. P. Bourman; S. M. Eggins; R. Grün (Australian Journal of Earth Sciences, 2016)

An overview of ice storms and their impact in the United States - Samuel K. Degelia; Jordan I. Christian; Jeffrey B. Basara; Trevor J. Mitchell; Daniel F. Gardner; Sara E. Jackson; John C. Ragland; Hayden R. Mahan (International Journal of Climatology, 2016)
Ice storms, defined by the US National Weather Service as freezing rain accumulations over 0.635 cm (0.25 inch), are often costly and destructive. Formation processes include the classic ‘melting’ process and supercooled warm rain process. Freezing rain is most commonly found ahead of a warm front or occlusion, where warm air is lifted over a cold shallow layer near the surface. Other synoptic patterns conducive to freezing rain include arctic fronts, isentropic lift over an arctic air mass, and cold air damming. Causes of spatial and temporal variations in freezing rain include, but are not limited to, terrain and proximity to water. Areas with the most occurrences of freezing rain in the United States include the Pacific Northwest, Upper Midwest, and Northeast/Appalachian regions. Empirical forecasting methods and numerical weather prediction are currently used to predict freezing rain. Successful forecasting of ice storm events requires evaluation of the thermodynamic profile of the atmosphere. Local effects such as proximity to water and topography must be taken into account, and non‐linear processes such as latent heating and cooling must not be ignored. Ice accumulation can cause tree damage, which, in addition to breakage of electrical cables, can lead to power outages. Deposition of ice also impacts road, rail, and air travel, with associated economic costs due to lost hours as workers are unable to travel. Ice storms also provide a significant risk to human health and life, with falling debris and slippery surfaces being primary threats.

Differential migration and the link between winter latitude, timing of migration, and breeding in a songbird - Bradley K. Woodworth; Amy E. M. Newman; Sheela P. Turbek; Bryant C. Dossman; Keith A. Hobson; Leonard I. Wassenaar; Greg W. Mitchell; Nathaniel T. Wheelwright; D. Ryan Norris (Oecologia, 2016)

Dedicated Herbaceous Biomass Feedstock Genetics and Development - W. F. Anderson; G. Sarath; S. Edme; M. D. Casler; R. B. Mitchell; C. M. Tobias; A. L. Hale; S. E. Sattler; J. E. Knoll (BioEnergy Research, 2016)

Three African antelope species with varying water dependencies exhibit similar selective brain cooling - W. Maartin Strauss; Robyn S. Hetem; Duncan Mitchell; Shane K. Maloney; Leith C. R. Meyer; Andrea Fuller (Journal of Comparative Physiology B, 2016)

A major QTL corresponding to the Rk locus for resistance to root-knot nematodes in cowpea (Vigna unguiculata L. Walp.) - Bao-Lam Huynh; William C. Matthews; Jeffrey D. Ehlers; Mitchell R. Lucas; Jansen R. P. Santos; Arsenio Ndeve; Timothy J. Close; Philip A. Roberts (Theoretical and Applied Genetics, 2016)

Alternative approaches for addressing non-permanence in carbon projects: an application to afforestation and reforestation under the Clean Development Mechanism - Christopher S. Galik; Brian C. Murray; Stephen Mitchell; Phil Cottle (Mitigation and Adaptation Strategies for Global Change, 2016)

Aliidiomarina minuta sp. nov., a haloalkaliphilic bacterium that forms ultra-small cells under non-optimal conditions - Saad M. Farooqui; Mitchell H. Wright; Anthony C. Greene (Antonie van Leeuwenhoek, 2016)

Toward an integrated monitoring framework to assess the effects of tropical forest degradation and recovery on carbon stocks and biodiversity - Mercedes M. C. Bustamante; Iris Roitman; T. Mitchell Aide; Ane Alencar; Liana O. Anderson; Luiz Aragão; Gregory P. Asner; Jos Barlow; Erika Berenguer; Jeffrey Chambers; Marcos H. Costa; Thierry Fanin; et al. (Global Change Biology, 2016)
Tropical forests harbor a significant portion of global biodiversity and are a critical component of the climate system. Reducing deforestation and forest degradation contributes to global climate‐change mitigation efforts, yet emissions and removals from forest dynamics are still poorly quantified. We reviewed the main challenges to estimate changes in carbon stocks and biodiversity due to degradation and recovery of tropical forests, focusing on three main areas: (1) the combination of field surveys and remote sensing; (2) evaluation of biodiversity and carbon values under a unified strategy; and (3) research efforts needed to understand and quantify forest degradation and recovery. The improvement of models and estimates of changes of forest carbon can foster process‐oriented monitoring of forest dynamics, including different variables and using spatially explicit algorithms that account for regional and local differences, such as variation in climate, soil, nutrient content, topography, biodiversity, disturbance history, recovery pathways, and socioeconomic factors. Generating the data for these models requires affordable large‐scale remote‐sensing tools associated with a robust network of field plots that can generate spatially explicit information on a range of variables through time. By combining ecosystem models, multiscale remote sensing, and networks of field plots, we will be able to evaluate forest degradation and recovery and their interactions with biodiversity and carbon cycling. Improving monitoring strategies will allow a better understanding of the role of forest dynamics in climate‐change mitigation, adaptation, and carbon cycle feedbacks, thereby reducing uncertainties in models of the key processes in the carbon cycle, including their impacts on biodiversity, which are fundamental to support forest governance policies, such as Reducing Emissions from Deforestation and Forest Degradation.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Absence of hybridisation between Fuscospora species at a site in Arthur's Pass National Park, New Zealand - RD Smissen; C Mitchell; M Roth; PB Heenan (New Zealand Journal of Botany, 2015)
We analysed simple sequence repeat markers for a selection of red beech ( Fuscospora fusca ) and mountain beech ( Fuscospora cliffortioides ) trees growing together and for seeds collected from them. Our analysis detected neither hybrid trees nor hybrid seeds within our sample. We suggest pre‐zygotic reproductive isolating mechanisms such as differences in flowering time may be important in maintaining boundaries between Fuscospora species despite extensive sympatry.

Psychopharmacological characterisation of the successive negative contrast effect in rats - C. E. Phelps; E. N. Mitchell; D. J. Nutt; H. M. Marston; E. S. J. Robinson (Psychopharmacology, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

SNP development in North American burying beetles (Coleoptera: Silphidae): a tool to inform conservation decisions - Derek D. Houston; Kevin S. Mitchell; Jared W. Clouse; Peter J. Maughan; J. Curtis Creighton; Ashlee N. Smith; Seth M. Bybee; Mark C. Belk (Conservation Genetics Resources, 2015)

Cerambycid Beetle Species with Similar Pheromones are Segregated by Phenology and Minor Pheromone Components - Robert F. Mitchell; Peter F. Reagel; Joseph C. H. Wong; Linnea R. Meier; Weliton Dias Silva; Judith Mongold-Diers; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Functional, morphological, and apoptotic alterations in skeletal muscle of ARC deficient mice - Andrew S. Mitchell; Ian C. Smith; Daniel Gamu; Stefan Donath; A. Russell Tupling; Joe Quadrilatero (Apoptosis, 2015)

Antibiotic Degradation During Thermophilic Composting - S. M. Mitchell; J. L. Ullman; A. Bary; C. G. Cogger; A. L. Teel; R. J. Watts (Water, Air, & Soil Pollution, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Pollen‐based quantitative reconstructions of Holocene regional vegetation cover (plant‐functional types and land‐cover types) in Europe suitable for climate modelling - A.‐K. Trondman; M.‐J. Gaillard; F. Mazier; S. Sugita; R. Fyfe; A. B. Nielsen; C. Twiddle; P. Barratt; H. J. B. Birks; A. E. Bjune; L. Björkman; A. Broström; et al. (Global Change Biology, 2015)
We present quantitative reconstructions of regional vegetation cover in north‐western Europe, western Europe north of the Alps, and eastern Europe for five time windows in the Holocene [around 6k, 3k, 0.5k, 0.2k, and 0.05k calendar years before present ( bp )] at a 1° × 1° spatial scale with the objective of producing vegetation descriptions suitable for climate modelling. The REVEALS model was applied on 636 pollen records from lakes and bogs to reconstruct the past cover of 25 plant taxa grouped into 10 plant‐functional types and three land‐cover types [evergreen trees, summer‐green (deciduous) trees, and open land]. The model corrects for some of the biases in pollen percentages by using pollen productivity estimates and fall speeds of pollen, and by applying simple but robust models of pollen dispersal and deposition. The emerging patterns of tree migration and deforestation between 6k bp and modern time in the REVEALS estimates agree with our general understanding of the vegetation history of Europe based on pollen percentages. However, the degree of anthropogenic deforestation (i.e. cover of cultivated and grazing land) at 3k, 0.5k, and 0.2k bp is significantly higher than deduced from pollen percentages. This is also the case at 6k in some parts of Europe, in particular Britain and Ireland. Furthermore, the relationship between summer‐green and evergreen trees, and between individual tree taxa, differs significantly when expressed as pollen percentages or as REVEALS estimates of tree cover. For instance, when Pinus is dominant over Picea as pollen percentages, Picea is dominant over Pinus as REVEALS estimates. These differences play a major role in the reconstruction of European landscapes and for the study of land cover–climate interactions, biodiversity and human resources.

Time series analysis of forest carbon dynamics: recovery of Pinus palustris physiology following a prescribed fire - G. Starr; C. L. Staudhammer; H. W. Loescher; R. Mitchell; A. Whelan; J. K. Hiers; J. J. O’Brien (New Forests, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Environmental fate and exposure; neonicotinoids and fipronil - J.-M. Bonmatin; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; C. Krupke; M. Liess; E. Long; M. Marzaro; E. A. D. Mitchell; D. A. Noome; N. Simon-Delso; et al. (Environmental Science and Pollution Research, 2015)

Artificial watering points are focal points for activity by an invasive herbivore but not native herbivores in conservation reserves in arid Australia - Mike Letnic; Shawn W. Laffan; Aaron C. Greenville; Benjamin G. Russell; Bruce Mitchell; Peter J. S. Fleming (Biodiversity and Conservation, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Winter climate change affects growing‐season soil microbial biomass and activity in northern hardwood forests - Jorge Durán; Jennifer L. Morse; Peter M. Groffman; John L. Campbell; Lynn M. Christenson; Charles T. Driscoll; Timothy J. Fahey; Melany C. Fisk; Myron J. Mitchell; Pamela H. Templer (Global Change Biology, 2014)
Understanding the responses of terrestrial ecosystems to global change remains a major challenge of ecological research. We exploited a natural elevation gradient in a northern hardwood forest to determine how reductions in snow accumulation, expected with climate change, directly affect dynamics of soil winter frost, and indirectly soil microbial biomass and activity during the growing season. Soils from lower elevation plots, which accumulated less snow and experienced more soil temperature variability during the winter (and likely more freeze/thaw events), had less extractable inorganic nitrogen (N), lower rates of microbial N production via potential net N mineralization and nitrification, and higher potential microbial respiration during the growing season. Potential nitrate production rates during the growing season were particularly sensitive to changes in winter snow pack accumulation and winter soil temperature variability, especially in spring. Effects of elevation and winter conditions on N transformation rates differed from those on potential microbial respiration, suggesting that N‐related processes might respond differently to winter climate change in northern hardwood forests than C‐related processes.

Geomorphology of the western Ionian Sea between Sicily and Calabria, Italy - Rajasmita Goswami; Neil C. Mitchell; Andrea Argnani; Simon H. Brocklehurst (Geo-Marine Letters, 2014)

Investigation of Dry Powder Inhaler (DPI) Resistance and Aerosol Dispersion Timing on Emitted Aerosol Aerodynamic Particle Sizing by Multistage Cascade Impactor when Sampled Volume Is Reduced from Compendial Value of 4 L - Hlack Mohammed; Jan Arp; Frank Chambers; Mark Copley; Volker Glaab; Mark Hammond; Derek Solomon; Kerry Bradford; Theresa Russell; Yvonne Sizer; Steven C. Nichols; Daryl L. Roberts; et al. (AAPS PharmSciTech, 2014)

Switchgrass Response to Nitrogen Fertilizer Across Diverse Environments in the USA: a Regional Feedstock Partnership Report - C. O. Hong; V. N. Owens; D. Bransby; R. Farris; J. Fike; E. Heaton; S. Kim; H. Mayton; R. Mitchell; D. Viands (BioEnergy Research, 2014)

From egg to hatchling: preferential retention of fatty acid biomarkers in young‐of‐the‐year Port Jackson sharks Heterodontus portusjacksoni - C. L. Beckmann; J. G. Mitchell; L. Seuront; D.A.J. Stone; C. Huveneers (Journal of Fish Biology, 2014)
The muscle and liver fatty acid composition of young‐of‐the‐year ( YOY ) Port Jackson sharks Heterodontus portusjacksoni were investigated to determine the effects of a known dietary lipid source v . maternal input as demonstrated by egg yolk fatty acid profiles. Ten Heterodontus portusjacksoni egg yolks were collected in situ and compared with four hatched H. portusjacksoni fed a known diet in a controlled feeding experiment of 185 days. This study demonstrated that fatty acids are probably conservatively transferred from egg yolks to YOY H. portusjacksoni , while diet did not have a large effect on the fatty acid composition of the liver or muscle.

Towards a molecular basis of oligometastatic disease: potential role of micro-RNAs - Abhineet Uppal; Mark K. Ferguson; Mitchell C. Posner; Samuel Hellman; Nikolai N. Khodarev; Ralph R. Weichselbaum (Clinical & Experimental Metastasis, 2014)

Thermoregulatory plasticity in free-ranging vervet monkeys, Chlorocebus pygerythrus - Alwyn Lubbe; Robyn S. Hetem; Richard McFarland; Louise Barrett; Peter S. Henzi; Duncan Mitchell; Leith C. R. Meyer; Shane K. Maloney; Andrea Fuller (Journal of Comparative Physiology B, 2014)

Characterization of mitochondrial haplogroups in a large population-based sample from the United States - Sabrina L. Mitchell; Robert Goodloe; Kristin Brown-Gentry; Sarah A. Pendergrass; Deborah G. Murdock; Dana C. Crawford (Human Genetics, 2014)

The influence of a single bout of aerobic exercise on short-interval intracortical excitability - Ashleigh E. Smith; Mitchell R. Goldsworthy; Tessa Garside; Fiona M. Wood; Michael C. Ridding (Experimental Brain Research, 2014)

Observations on the crystal structures of lueshite - Roger H. Mitchell; Peter C. Burns; Kevin S. Knight; Christopher J. Howard; Anton R. Chakhmouradian (Physics and Chemistry of Minerals, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Evaluating Cenozoic equatorial sediment deposition anomalies for potential paleoceanographic and Pacific plate motion applications - Neil C. Mitchell; Nathalie Dubois (Marine Geophysical Research, 2014)

When depth is no refuge: cumulative thermal stress increases with depth in Bocas del Toro, Panama - B. P. Neal; C. Condit; G. Liu; S. dos Santos; M. Kahru; B. G. Mitchell; D. I. Kline (Coral Reefs, 2014)

The value of plantation forests for plant, invertebrate and bird diversity and the potential for cross-taxon surrogacy - Sandra Irwin; Scott M. Pedley; Linda Coote; Anke C. Dietzsch; Mark W. Wilson; Anne Oxbrough; Oisín Sweeney; Karen M. Moore; Rebecca Martin; Daniel L. Kelly; Fraser J. G. Mitchell; Thomas C. Kelly; et al. (Biodiversity and Conservation, 2014)

Circulating acylcarnitines as biomarkers of mitochondrial dysfunction after acetaminophen overdose in mice and humans - Mitchell R. McGill; Feng Li; Matthew R. Sharpe; C. David Williams; Steven C. Curry; Xiaochao Ma; Hartmut Jaeschke (Archives of Toxicology, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Temperature impacts on anaerobic biotransformation of LNAPL and concurrent shifts in microbial community structure - Natalie R. Zeman; Maria Irianni Renno; Mitchell R. Olson; L. Paige Wilson; Thomas C. Sale; Susan K. De Long (Biodegradation, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

The incidence of PALB2 c.3113G>A in women with a strong family history of breast and ovarian cancer attending familial cancer centres in Australia - Zhi L. Teo; Sarah D. Sawyer; Paul A. James; Gillian Mitchell; Alison H. Trainer; Geoffrey J. Lindeman; Kylie Shackleton; Linda Cicciarelli; Melissa C. Southey (Familial Cancer, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Community‐specific impacts of exotic earthworm invasions on soil carbon dynamics in a sandy temperate forest - Jasmine M. Crumsey; James M. Le Moine; Yvan Capowiez; Mitchell M. Goodsitt; Sandra C Larson; George W. Kling; Knute J. Nadelhoffer (Ecology, 2013)
Exotic earthworm introductions can alter above‐ and belowground properties of temperate forests, but the net impacts on forest soil carbon (C) dynamics are poorly understood. We used a mesocosm experiment to examine the impacts of earthworm species belonging to three different ecological groups ( Lumbricus terrestris [anecic], Aporrectodea trapezoides [endogeic], and Eisenia fetida [epigeic]) on C distributions and storage in reconstructed soil profiles from a sandy temperate forest soil by measuring CO 2 and dissolved organic carbon (DOC) losses, litter C incorporation into soil, and soil C storage with monospecific and species combinations as treatments. Soil CO 2 loss was 30% greater from the Endogeic × Epigeic treatment than from controls (no earthworms) over the first 45 days; CO 2 losses from monospecific treatments did not differ from controls. DOC losses were three orders of magnitude lower than CO 2 losses, and were similar across earthworm community treatments. Communities with the anecic species accelerated litter C mass loss by 31–39% with differential mass loss of litter types ( Acer rubrum > Populus grandidentata > Fagus grandifolia > Quercus rubra ≥ Pinus strobus ) indicative of leaf litter preference. Burrow system volume, continuity, and size distribution differed across earthworm treatments but did not affect cumulative CO 2 or DOC losses. However, burrow system structure controlled vertical C redistribution by mediating the contributions of leaf litter to A‐horizon C and N pools, as indicated by strong correlations between (1) subsurface vertical burrows made by anecic species, and accelerated leaf litter mass losses (with the exception of P. strobus ); and (2) dense burrow networks in the A‐horizon and the C and N properties of these pools. Final soil C storage was slightly lower in earthworm treatments, indicating that increased leaf litter C inputs into soil were more than offset by losses as CO 2 and DOC across earthworm community treatments.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

The new sequencer on the block: comparison of Life Technology’s Proton sequencer to an Illumina HiSeq for whole-exome sequencing - Joseph F. Boland; Charles C. Chung; David Roberson; Jason Mitchell; Xijun Zhang; Kate M. Im; Ji He; Stephen J. Chanock; Meredith Yeager; Michael Dean (Human Genetics, 2013)

Population genetics and ethnobotany of cultivated Diospyros riojae Gómez Pompa (Ebenaceae), an endangered fruit crop from Mexico - Mitchell C. Provance; Ignacio García-Ruiz; Casper Thommes; Jeffrey Ross-Ibarra (Genetic Resources and Crop Evolution, 2013)

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Sewage reflects the distribution of human faecal L achnospiraceae - Sandra L. McLellan; Ryan J. Newton; Jessica L. Vandewalle; Orin C. Shanks; Susan M. Huse; A. Murat Eren; Mitchell L. Sogin (Environmental Microbiology, 2013)
Summary Faecal pollution contains a rich and diverse community of bacteria derived from animals and humans, many of which might serve as alternatives to the traditional enterococci and E scherichia coli faecal indicators. We used massively parallel sequencing ( MPS ) of the 16 S rRNA gene to characterize microbial communities from wastewater treatment plant ( WWTP ) influent sewage from 12 cities geographically distributed across the USA . We examined members of the C lostridiales , which included the families C lostridiaceae , L achnospiraceae and R uminococcaceae for their potential as sewage indicators. L achnospiraceae was one of the most abundant groups of faecal bacteria in sewage, and several L achnospiraceae high‐abundance sewage pyrotags occurred in at least 46 of 48 human faecal samples. Clone libraries targeting C lostridium coccoides ( C . coccoides ) in sewage samples demonstrated that Lachnospiraceae ‐annotated V 6 pyrotags encompassed the previously reported C . coccoides group. We used oligotyping to profile the genus B lautia within L achnospiraceae and found oligotypes comprised of 24 entropy components that showed patterns of host specificity. These findings suggest that indicators based on B lautia might have the capacity to discriminate between different faecal pollution sources. Development of source‐specific alternative indicators would enhance water quality assessments, which leads to improved ecosystem health and reduced human health risk due to waterborne disease.

Engineered applications of ureolytic biomineralization: a review - Adrienne J. Phillips; Robin Gerlach; Ellen Lauchnor; Andrew C. Mitchell; Alfred B. Cunningham; Lee Spangler (Biofouling, 2013)

Differential patterns of mono- and sesquiterpenes with leaf ontogeny influence pharmaceutical oil yield in Eucalyptus polybractea R.T. Baker - Jason Q. D. Goodger; Madeline C. Mitchell; Ian E. Woodrow (Trees, 2013)

Stable carbon isotopic evidence for climate change across the late Pleistocene to early Holocene from Lesotho, southern Africa - P. ROBERTS; J. A. LEE‐THORP; P. J. MITCHELL; C. ARTHUR (Journal of Quaternary Science, 2013)
Although significant environmental and climatic changes are likely to have occurred across the Pleistocene/Holocene transition in southern Africa, records are sparse, with information regarding temperature change especially rare. We thus know little about the conditions facing Later Stone Age human populations at this time, particularly those in the highland interior where temperature shifts would have had strong impacts on floral and faunal distributions. In Lesotho, a well‐defined altitudinal distribution of C 3 and C 4 photosynthetic plant taxa, and their remains in soil organic matter, provides a means of estimating past temperature shifts. We applied this principle to stratified sediments from two archaeological sequences in the Lesotho lowlands ( c . 1600 m a.s.l.) to produce a palaeotemperature record focusing on the period 14 000–9500 cal a BP. The results show an overall trend from exclusively C 3 vegetation at the Last Glacial Maximum towards greater contributions of C 4 taxa, and thus warmer conditions, during the Holocene. However, large temperature fluctuations are evident within this trend, with rapid changes of up to 4 °C visible between 11 200 and 9500 cal a BP. The continued presence of hunter‐gatherers during this time suggests that the region must have remained attractive to human populations despite significant climatic instability and cool episodes. Copyright © 2013 John Wiley & Sons, Ltd.

Macroecological patterns of marine bacteria on a global scale - Anthony S. Amend; Tom A. Oliver; Linda A. Amaral‐Zettler; Antje Boetius; Jed A. Fuhrman; M. Claire Horner‐Devine; Susan M. Huse; David B. Mark Welch; Adam C. Martiny; Alban Ramette; Lucie Zinger; Mitchell L. Sogin; et al. (Journal of Biogeography, 2013)
Aim To test whether within‐species and among‐species patterns of abundance and latitudinal range in marine bacteria resemble those found for macro‐organisms, and whether these patterns differ along latitudinal clines. Location Global pelagic marine environments. Methods Taxon‐specific sequence abundance and location were retrieved from the open‐access V6‐ rRNA pyrotag sequence data base VAMPS ( http://vamps.mbl.edu/ ), which holds a massive collection of marine bacterial community data sets from the I nternational C ensus of M arine M icrobes sampling effort of global ocean water masses. Data were randomly subsampled to correct for spatial bias and for differences in sampling effort. Results We show that bacterial latitudinal ranges are narrower than expected by chance. When present in both N orthern and S outhern hemispheres, taxa occupy restricted ranges at similar latitudes on both sides of the equator. A significant and positive relationship exists between sequence abundance and latitudinal range, although this pattern contains a large amount of variance. Abundant taxa in the tropics and in the N orthern H emisphere generally have smaller ranges than those in the S outhern H emisphere. We show that the mean latitudinal range of bacterial taxa increases with latitude, supporting the existence of a R apoport effect in marine bacterioplankton. Finally, we show that bacterioplankton communities contain a higher proportion of abundant taxa as they approach the poles. Main conclusions Macroecological patterns such as the abundance–range relationship, in general, extend to marine bacteria. However, differences in the shape of these relationships between bacteria and macro‐organisms call into question whether the processes and their relative importance in shaping global marine bacteria and macro‐organism distributions are the same.

Long-term continuous measurement of near-road air pollution in Las Vegas: seasonal variability in traffic emissions impact on local air quality - Sue Kimbrough; Richard W. Baldauf; Gayle S. W. Hagler; Richard C. Shores; William Mitchell; Donald A. Whitaker; Carry W. Croghan; Daniel A. Vallero (Air Quality, Atmosphere & Health, 2013)

Good Cascade Impactor Practice (GCIP) and Considerations for “In-Use” Specifications - S. C. Nichols; J. P. Mitchell; C. M. Shelton; D. L. Roberts (AAPS PharmSciTech, 2013)

Lentiviral-mediated over-expression of hyaluronan synthase-1 (HAS-1) decreases the cellular inflammatory response and results in regenerative wound repair - Robert C. Caskey; Myron Allukian; Robert C. Lind; Benjamin J. Herdrich; Junwang Xu; Antoneta Radu; Marc E. Mitchell; Kenneth W. Liechty (Cell and Tissue Research, 2013)

Current state of knowledge regarding the world’s wetlands and their future under global climate change: a synthesis - Wolfgang J. Junk; Shuqing An; C. M. Finlayson; Brij Gopal; Jan Květ; Stephen A. Mitchell; William J. Mitsch; Richard D. Robarts (Aquatic Sciences, 2013)

Cone morphologies associated with shallow marine eruptions: east Pico Island, Azores - Neil C. Mitchell; Rachelle Stretch; Clive Oppenheimer; Daniel Kay; Christoph Beier (Bulletin of Volcanology, 2012)

Securing the Demographic and Genetic Future of Tuatara through Assisted Colonization - KIMBERLY A. MILLER; HILARY C. MILLER; JENNIFER A. MOORE; NICOLA J. MITCHELL; ALISON CREE; FRED W. ALLENDORF; STEPHEN D. SARRE; SUSAN N. KEALL; NICOLA J. NELSON (Conservation Biology, 2012)
Climate change poses a particular threat to species with fragmented distributions and little or no capacity to migrate. Assisted colonization, moving species into regions where they have not previously occurred, aims to establish populations where they are expected to survive as climatic envelopes shift. However, adaptation to the source environment may affect whether species successfully establish in new regions. Assisted colonization has spurred debate among conservation biologists and ecologists over whether the potential benefits to the threatened species outweigh the potential disruption to recipient communities. In our opinion, the debate has been distracted by controversial examples, rather than cases where assisted colonization may be a viable strategy. We present a strategic plan for the assisted migration of tuatara ( Sphenodon punctatus ), an endemic New Zealand reptile. The plan includes use of extant populations as reference points for comparisons with assisted‐colonization populations with respect to demography, phenotypic plasticity, and phenology; optimization of genetic variation; research to fill knowledge gaps; consideration of host and recipient communities; and inclusion of stakeholders in the planning stage. When strategically planned and monitored, assisted colonization could meet conservation and research goals and ultimately result in the establishment of long‐term sustainable populations capable of persisting during rapid changes in climate.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Cash, food, or vouchers? An application of the Market Information and Food Insecurity Response Analysis Framework in urban and rural Kenya - Hope Michelson; Erin C. Lentz; Richard Mulwa; Mitchell Morey; Laura Cramer; Megan McGlinchy; Christopher B. Barrett (Food Security, 2012)

The first report of Spondias native to Madagascar: Spondias tefyi, sp. nov. (Anacardiaceae) - John D. Mitchell; Douglas C. Daly; Armand Randrianasolo (Brittonia, 2012)

Effect of Sampling Volume on Dry Powder Inhaler (DPI)-Emitted Aerosol Aerodynamic Particle Size Distributions (APSDs) Measured by the Next-Generation Pharmaceutical Impactor (NGI) and the Andersen Eight-Stage Cascade Impactor (ACI) - Hlack Mohammed; Daryl L. Roberts; Mark Copley; Mark Hammond; Steven C. Nichols; Jolyon P. Mitchell (AAPS PharmSciTech, 2012)

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Evaluation of methods for achieving stable INR in healthy subjects during a multiple-dose warfarin study - Jill C. Chappell; Gemma Dickinson; Malcolm I. Mitchell; Harry Haber; Yan Jin; Evelyn D. Lobo (European Journal of Clinical Pharmacology, 2012)

Assessing landslide movements in volcanic islands using near-shore marine geophysical data: south Pico island, Azores - Neil C. Mitchell; Rui Quartau; José Madeira (Bulletin of Volcanology, 2012)

Metagenomic comparison of microbial communities inhabiting confined and unconfined aquifer ecosystems - Renee J. Smith; Thomas C. Jeffries; Ben Roudnew; Alison J. Fitch; Justin R. Seymour; Marina W. Delpin; Kelly Newton; Melissa H. Brown; James G. Mitchell (Environmental Microbiology, 2012)
Summary A metagenomic analysis of two aquifer systems located under a dairy farming region was performed to examine to what extent the composition and function of microbial communities varies between confined and surface‐influenced unconfined groundwater ecosystems. A fundamental shift in taxa was seen with an overrepresentation of Rhodospirillales , Rhodocyclales , Chlorobia and Circovirus in the unconfined aquifer, while Deltaproteobacteria and Clostridiales were overrepresented in the confined aquifer. A relative overrepresentation of metabolic processes including antibiotic resistance (β‐lactamase genes), lactose and glucose utilization and DNA replication were observed in the unconfined aquifer, while flagella production, phosphate metabolism and starch uptake pathways were all overrepresented in the confined aquifer. These differences were likely driven by differences in the nutrient status and extent of exposure to contaminants of the two groundwater systems. However, when compared with freshwater, ocean, sediment and animal gut metagenomes, the unconfined and confined aquifers were taxonomically and metabolically more similar to each other than to any other environment. This suggests that intrinsic features of groundwater ecosystems, including low oxygen levels and a lack of sunlight, have provided specific niches for evolution to create unique microbial communities. Obtaining a broader understanding of the structure and function of microbial communities inhabiting different groundwater systems is particularly important given the increased need for managing groundwater reserves of potable water.

Time-Dependent Impacts of Cattail Invasion in a Great Lakes Coastal Wetland Complex - Mark E. Mitchell; Shane C. Lishawa; Pamela Geddes; Daniel J. Larkin; David Treering; Nancy C. Tuchman (Wetlands, 2011)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

Using microsatellite diversity in wild Anegada iguanas (Cyclura pinguis) to establish relatedness in a captive breeding group of this critically endangered species - Adele A. Mitchell; Jennie Lau; Leona G. Chemnick; Elizabeth A. Thompson; Allison C. Alberts; Oliver A. Ryder; Glenn P. Gerber (Conservation Genetics, 2011)

Development of a multiplexed bead-based immunoassay for the simultaneous detection of antibodies to 17 pneumococcal proteins - S. Shoma; N. J. Verkaik; C. P. de Vogel; P. W. M. Hermans; S. van Selm; T. J. Mitchell; M. van Roosmalen; S. Hossain; M. Rahman; H. Ph. Endtz; W. J. B. van Wamel; A. van Belkum (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Postdiagnosis diet quality, the combination of diet quality and recreational physical activity, and prognosis after early-stage breast cancer - Stephanie M. George; Melinda L. Irwin; Ashley W. Smith; Marian L. Neuhouser; Jill Reedy; Anne McTiernan; Catherine M. Alfano; Leslie Bernstein; Cornelia M. Ulrich; Kathy B. Baumgartner; Steven C. Moore; Demetrius Albanes; et al. (Cancer Causes & Control, 2011)

Developing next-generation climate change scholars: the DISCCRS experience - Ronald B. Mitchell; C. Susan Weiler (Journal of Environmental Studies and Sciences, 2011)

The influence of aerobic exercise training on the double product break point in low-to-moderate risk adults - Trent A. Hargens; Diane C. Griffin; Leonard A. Kaminsky; Mitchell H. Whaley (European Journal of Applied Physiology, 2011)

Seroprevalence of seasonal and pandemic influenza A viruses in domestic cats - Jonathan A. McCullers; Lee-Ann Van De Velde; Ronald D. Schultz; Cristen G. Mitchell; C. R. Halford; Kelli L. Boyd; Stacey Schultz-Cherry (Archives of Virology, 2011)

Sustained cortical and subcortical neuromodulation induced by electrical tongue stimulation - Joseph C. Wildenberg; Mitchell E. Tyler; Yuri P. Danilov; Kurt A. Kaczmarek; Mary E. Meyerand (Brain Imaging and Behavior, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Linear increases in BOLD response associated with increasing proportion of incongruent trials across time in a colour Stroop task - Rachel L. C. Mitchell (Experimental Brain Research, 2010)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Ultraviolet radiation affects invasibility of lake ecosystems by warm‐water fish - Andrew J. Tucker; Craig E. Williamson; Kevin C. Rose; James T. Oris; Sandra J. Connelly; Mark H. Olson; David L. Mitchell (Ecology, 2010)
Predicting where species invasions will occur remains a substantial challenge in ecology, but identifying factors that ultimately constrain the distribution of potential invaders could facilitate successful prediction. Whereas ultraviolet radiation (UVR) is recognized as an important factor controlling species distribution and community composition, the role of UVR in a habitat invasibility context has not been explored. Here we examine how underwater UVR can regulate warm‐water fish invasion. In Lake Tahoe, California and Nevada, USA, established populations of exotic bluegill sunfish ( Lepomis macrochirus ) are currently limited to turbid, low‐UVR embayments. An in situ incubation experiment that manipulated incident UVR exposure of larval bluegill, combined with an assessment of UVR exposure levels in nearshore habitats around Lake Tahoe, demonstrates that UVR can mediate habitat invasibility. Our findings suggest that the susceptibility to invasion by UVR sensitive species may increase in transparent aquatic systems threatened by declining water quality, and they highlight the importance of abiotic factors as regulators of invasion risk in ecosystems.

Sustained Release of Multiple Growth Factors from Injectable Polymeric System as a Novel Therapeutic Approach Towards Angiogenesis - Qinghua Sun; Eduardo A Silva; Aixia Wang; James C. Fritton; David J. Mooney; Mitchell B. Schaffler; Paul M. Grossman; Sanjay Rajagopalan (Pharmaceutical Research, 2010)

Genetic diversity and population structure analysis of accessions in the US historic sweet sorghum collection - Ming L. Wang; Chengsong Zhu; Noelle A. Barkley; Zhenbang Chen; John E. Erpelding; Seth C. Murray; Mitchell R. Tuinstra; Tesfaye Tesso; Gary A. Pederson; Jianming Yu (Theoretical and Applied Genetics, 2009)

Design, synthesis, and docking studies of telmisartan analogs for the treatment of metabolic syndrome - Cassia S. Mizuno; Amar G. Chittiboyina; Akshay Patny; Theodore W. Kurtz; Harrihar A. Pershadsingh; Robert C. Speth; Vardan T. Karamyan; Mitchell A. Avery (Medicinal Chemistry Research, 2009)

Glucokinase regulatory protein gene polymorphism affects postprandial lipemic response in a dietary intervention study - Haiqing Shen; Toni I. Pollin; Coleen M. Damcott; John C. McLenithan; Braxton D. Mitchell; Alan R. Shuldiner (Human Genetics, 2009)

Subacute exposure to N-ethyl perfluorooctanesulfonamidoethanol results in the formation of perfluorooctanesulfonate and alters superoxide dismutase activity in female rats - Wei Xie; Qian Wu; Izabela Kania-Korwel; Job C. Tharappel; Sanjay Telu; Mitchell C. Coleman; Howard P. Glauert; Kurunthachalam Kannan; S. V. S. Mariappan; Douglas R. Spitz; Jamie Weydert; Hans-Joachim Lehmler (Archives of Toxicology, 2009)

Design, synthesis, and docking studies of novel telmisartan–glitazone hybrid analogs for the treatment of metabolic syndrome - Amar G. Chittiboyina; Cassia S. Mizuno; Prashant V. Desai; Akshay Patny; Theodore W. Kurtz; Harrihar A. Pershadsingh; Robert C. Speth; Vardan Karamyan; Mitchell A. Avery (Medicinal Chemistry Research, 2009)

A pilot study on iodine in soils of Greater Kabul and Nangarhar provinces of Afghanistan - M. J. Watts; C. J. Mitchell (Environmental Geochemistry and Health, 2009)

Life history in a model system: opening the black box with Arabidopsis thaliana - C. Jessica E. Metcalf; Thomas Mitchell‐Olds (Ecology Letters, 2009)
A broad research programme in Arabidopsis thaliana has provided estimates of selection on specific alleles in specific contexts, and identified geographic patterns of alleles in genes linked to timing of flowering. A closely related field has successfully captured many key axes of the evolution of timing of flowering in other monocarpic species through statistical and demographic modelling of large empirical databases. There has as yet been no synthesis between these two fields. Here we examine ways in which the two fields inform each other, and how this synergy will shape our knowledge of life‐history evolution as a whole.

Linkages between environmental conditions and recreational king mackerel ( Scomberomorus cavalla ) catch off west‐central Florida - CARRIE C. WALL; FRANK E. MULLER‐KARGER; MITCHELL A. ROFFER (Fisheries Oceanography, 2009)
Catch statistics for the king mackerel ( Scomberomorus cavalla ) recreational fishery off west‐central Florida were derived from angler interviews conducted during 19 seasonal tournaments held in April–May and October–November of 2004 and 2005. Fishing location, number of fish per line per hour (catch per unit effort), and presence of baitfish from the tournament data were examined in the context of bathymetric gradients and other benthic features (e.g., wrecks or artificial reefs), and the location and persistence of oceanic fronts mapped using satellite imagery of sea surface temperature (AVHRR) and ocean color (MODIS and SeaWiFS). Generalized linear models were applied to identify the relationship between king mackerel catch rates and environmental data. The distance of fishing activity to the nearest front varied substantially, particularly when winds and front position were variable. However, baitfish presence with proximity to water clarity fronts (as defined by water‐leaving radiance at 443 nm) significantly influenced successful king mackerel catch. Positive catch rates were significantly influenced by chlorophyll values and period (season and year). Additionally, intermediate water clarity (in the range 0.7–1.0 mW cm −2 μm −1 sr −1 ) led to higher catch rates. Decreased water quality, primarily associated with a large Karenia brevis red tide, led to a lower number of catch and lower catch rates (122 king mackerel, 0.13 catch per unit effort) in fall 2005, compared to spring 2004 (179, 0.14), fall 2004 (360, 0.17) and spring 2005 (296, 0.21), despite a consistent seasonal effort.

Brain thermal inertia, but no evidence for selective brain cooling, in free-ranging western grey kangaroos (Macropus fuliginosus) - Shane K. Maloney; Andrea Fuller; Leith C. R. Meyer; Peter R. Kamerman; Graham Mitchell; Duncan Mitchell (Journal of Comparative Physiology B, 2009)

The crystal structure of auracyanin A at 1.85 Å resolution: the structures and functions of auracyanins A and B, two almost identical “blue” copper proteins, in the photosynthetic bacterium Chloroflexus aurantiacus - Mihwa Lee; Melissa C. del Rosario; Hugh H. Harris; Robert E. Blankenship; J. Mitchell Guss; Hans C. Freeman (JBIC Journal of Biological Inorganic Chemistry, 2009)

Effects of nutrients and dissolved organic matter on the response of phytoplankton to ultraviolet radiation: experimental comparison in spring versus summer - Caren E. Scott; Jasmine E. Saros; Craig E. Williamson; Courtney R. Salm; Stephen C. Peters; David L. Mitchell (Hydrobiologia, 2009)

Identifying important biophysical and social determinants of on-farm tree growing in subsistence-based traditional agroforestry systems - Kamal Kishor Sood; C. Paul Mitchell (Agroforestry Systems, 2009)

Risk Management in the Pharmaceutical Product Development Process - Matthew H. Hulbert; Liam C. Feely; Eugene L. Inman; Alton D. Johnson; Albert S. Kearney; James Michaels; Michael Mitchell; Elena Zour (Journal of Pharmaceutical Innovation, 2008)

Increased nitric oxide synthase activity and Hsp90 association in skeletal muscle following chronic exercise - M. Brennan Harris; Brett M. Mitchell; Sarika G. Sood; R. Clinton Webb; Richard C. Venema (European Journal of Applied Physiology, 2008)

Transgenic maize plants expressing a fungal phytase gene - Rumei Chen; Guangxing Xue; Ping Chen; Bin Yao; Wenzhu Yang; Qianli Ma; Yunliu Fan; Zuoyu Zhao; Mitchell C. Tarczynski; Jinrui Shi (Transgenic Research, 2008)

Long-term changes in management following n-of-1 trials of stimulants in attention-deficit/hyperactivity disorder - C. Jane Nikles; Geoffrey K. Mitchell; Chris B. Del Mar; Norma McNairn; Alexandra Clavarino (European Journal of Clinical Pharmacology, 2007)

Purification and characterization of rhodobactin: a mixed ligand siderophore from Rhodococcus rhodochrous strain OFS - Suraj Dhungana; Ryszard Michalczyk; Hakim Boukhalfa; Joseph G. Lack; Andrew T. Koppisch; Jason M. Fairlee; Mitchell T. Johnson; Christy E. Ruggiero; Seth G. John; Matthew M. Cox; Cindy C. Browder; Jennifer H. Forsythe; et al. (BioMetals, 2007)

The influence of the balance of inorganic and organic nitrogen on the trophic dynamics of microbial food webs - Keith Davidson; Linda C. Gilpin; Mark C. Hart; Eric Fouilland; Elaine Mitchell; Ignacio Á lvarez Calleja; CÉline Laurent; Axel E. J. Miller; Raymond J. G. Leakey (Limnology and Oceanography, 2007)
A nutrient‐manipulation mesocosm study was conducted in Norwegian coastal waters to determine the effect on a nitrogen‐limited microbial food web of changes in the relative concentrations of dissolved organic and inorganic nitrogen (N). Four replicated treatments were studied: no N addition, inorganic N, organic N, or a 50 : 50 mix of inorganic and organic N. Comprehensive abundance, biomass, and rate measurements were made over the 20‐d experiment. The form of N available influenced species composition, succession, and the efficiency of carbon (C) incorporation. Inorganic N generated a bloom of the diatom Leptocylindrus danicus , even though silicon concentrations were below 1 µmol L −1 . The c‐proteobacteria initially competed effectively with diatoms for inorganic N, exhibiting high productivity and escaping grazing control. Organic N, when available alone, was utilized more slowly by the microbial community, with diatom growth, fueled by regenerated N, achieving a lower peak abundance. A more diverse diatom species assemblage was also evident. The γ‐proteobacteria were less prevalent and net bacterial productivity was initially lower when the N source was organic and, in contrast to the response following inorganic N addition, the bacterial community was initially grazer controlled. A rapid succession of heterotrophic grazers occurred but with differences in species and their contribution to biomass between treatments. The efficiency of C‐biomass production was lower when the N source was purely organic. However, when both inorganic and organic N were available, biomass yield was greater than the mean of the two single N source treatments.

Scale-specific correlations between habitat heterogeneity and soil fauna diversity along a landscape structure gradient - Adam J. Vanbergen; Allan D. Watt; Ruth Mitchell; Anne-Marie Truscott; Stephen C. F. Palmer; Eva Ivits; Paul Eggleton; T. Hefin Jones; José Paulo Sousa (Oecologia, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Urban Influences on Stream Chemistry and Biology in the Big Brushy Creek Watershed, South Carolina - Gregory P. Lewis; Jennifer D. Mitchell; C. Brannon Andersen; Dennis C. Haney; Min-Ken Liao; Kenneth A. Sargent (Water, Air, & Soil Pollution, 2007)

Comparison between ATSR‐2 stereo, MOS O 2 ‐A band and ground‐based cloud top heights - C. Naud; K. L. Mitchell; J.‐P. Muller; E. E. Clothiaux; P. Albert; R. Preusker; J. Fischer; R. J. Hogan (International Journal of Remote Sensing, 2007)

Stereo cloud‐top heights and cloud fraction retrieval from ATSR‐2 - J.‐P. Muller; M.‐A. Denis; R. D. Dundas; K. L. Mitchell; C. Naud; H. Mannstein (International Journal of Remote Sensing, 2007)

Sex differences in the potency of κ opioids and mixed-action opioids administered systemically and at the site of inflammation against capsaicin-induced hyperalgesia in rats - Lisa M. Lomas; Andrew C. Barrett; Jolan M. Terner; Donald T. Lysle; Mitchell J. Picker (Psychopharmacology, 2007)

West Nile virus encephalitis: sequential histopathological and immunological events in a murine model of infection - David Garcia-Tapia; Daniel E Hassett; William J Mitchell; Gayle C Johnson; Steven B Kleiboeker (Journal of NeuroVirology, 2007)

Unique vascular phenotypes following over-expression of individual VEGFA isoforms from the developing lens - Christopher A. Mitchell; Catrin S. Rutland; Michael Walker; Muneeb Nasir; Alexander J. E. Foss; Christine Stewart; Holger Gerhardt; Moritz A. Konerding; Werner Risau; Hannes C. A. Drexler (Angiogenesis, 2006)

Quantifying anthropogenic influence on recent near-surface temperature change - M. R. Allen; N. P. Gillett; J. A. Kettleborough; G. Hegerl; R. Schnur; P. A. Stott; G. Boer; C. Covey; T. L. Delworth; G. S. Jones; J. F. B. Mitchell; T. P. Barnett (Surveys in Geophysics, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Nitric oxide accelerates seed germination in warm-season grasses - Gautam Sarath; Paul C. Bethke; Russell Jones; Lisa M. Baird; Guichuan Hou; Robert B. Mitchell (Planta, 2006)

Dissociation between sex differences in the immunological, behavioral, and physiological effects of κ- and δ-opioids in Fischer rats - Jay C. Elliott; Mitchell J. Picker; Andrew J. Sparrow; Donald T. Lysle (Psychopharmacology, 2006)

The Homeobox Gene GLABRA2 Affects Seed Oil Content in Arabidopsis - Bo Shen; Kerstin W. Sinkevicius; David A. Selinger; Mitchell C. Tarczynski (Plant Molecular Biology, 2006)

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Diversity in the sunflower: Puccinia helianthi pathosystem in Australia - B. C. Sendall; G. A. Kong; K. C. Goulter; E. A. B. Aitken; S. M. Thompson; J. H. M. Mitchell; J. K. Kochman; W. Lawson; T. Shatte; T. J. Gulya (Australasian Plant Pathology, 2006)

An oral carcinogenicity and toxicity study of senna (Tinnevelly senna fruits) in the rat - J. M. Mitchell; U. Mengs; S. McPherson; J. Zijlstra; P. Dettmar; R. Gregson; J. C. Tigner (Archives of Toxicology, 2006)

The role of 5′-adenylylsulfate reductase in controlling sulfate reduction in plants - Melinda N. Martin; Mitchell C. Tarczynski; Bo Shen; Thomas Leustek (Photosynthesis Research, 2005)

Molecular characterization of sulfate‐reducing bacteria in a New England salt marsh - Michele Bahr; Byron C. Crump; Vanja Klepac‐Ceraj; Andreas Teske; Mitchell L. Sogin; John E. Hobbie (Environmental Microbiology, 2005)
Summary Sulfate reduction, mediated by sulfate‐reducing bacteria (SRB), is the dominant remineralization pathway in sediments of New England salt marshes. High sulfate reduction rates are associated with the rhizosphere of Spartina alterniflora when plants elongate aboveground. The growth process concurrently produces significant amounts of new rhizome material belowground and the plants leak dissolved organic compounds. This study investigated the diversity of SRB in a salt marsh over an annual growth cycle of S. alterniflora by exploring the diversity of a functional gene, dissimilatory sulfite reductase ( dsrAB ). Because the dsrAB gene is a key gene in the anaerobic sulfate‐respiration pathway, it allows the identification of microorganisms responsible for sulfate reduction. Conserved dsrAB primers in polymerase chain reaction (PCR) generated full‐length dsrAB amplicons for cloning and DNA sequence analysis. Nearly 80% of 380 clone sequences were similar to genes from Desulfosarcina and Desulfobacterium species within Desulfobacteraceae. This reinforces the hypothesis that complete oxidizers with high substrate versatility dominate the marsh . However, the phylotypes formed several clades that were distinct from cultured representatives, indicating a greater diversity of SRB than previously appreciated. Several dsrAB sequences were related to homologues from Gram‐positive, thermophilic and non‐thermophilic Desulfotomaculum species. One dsrAB lineage formed a sister group to cultured members of the delta‐proteobacterial group Syntrophobacteraceae . A deeply branching dsrAB lineage was not affiliated with genes from any cultured SRB. The sequence data from this study will allow for the design of probes or primers that can quantitatively assess the diverse range of sulfate reducers present in the environment.

Decomposition of chestnut oak (Quercus prinus) leaves and nitrogen mineralization in an urban environment - Mitchell A. Pavao-Zuckerman; David C. Coleman (Biology and Fertility of Soils, 2005)

Diversity and selection in sorghum: simultaneous analyses using simple sequence repeats - A. M. Casa; S. E. Mitchell; M. T. Hamblin; H. Sun; J. E. Bowers; A. H. Paterson; C. F. Aquadro; S. Kresovich (Theoretical and Applied Genetics, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Antidepressant-like effects of the nociceptin/orphanin FQ receptor antagonist UFP-101: new evidence from rats and mice - E. C. Gavioli; C. W. Vaughan; G. Marzola; R. Guerrini; V. A. Mitchell; S. Zucchini; T. C. M. De Lima; G. A. Rae; S. Salvadori; D. Regoli; G. Calo’ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Fine Root Carbon Allocation and Fates in Longleaf Pine Forests - Durwin C. Carter; Joseph J. Hendricks; Robert J. Mitchell; Stephen D. Pecot (Forest Science, 2004)
The patterns and mechanistic controls of fine root production and mortality in a 19-year-old longleaf pine (Pinus palustris Miller) plantation were assessed using minirhizotrons in a complete factorial design experiment that manipulated root carbon source and sink strengths. Carbon source strength to roots was manipulated through foliar scorching, carbon sink strength in roots was altered via nitrogen fertilization, and carbon transfer from roots to the soil organic matter pool was impacted using a general soil pesticide to distinguish between root mortality via herbivory and senescence. Fertilization significantly increased fine root nitrogen concentrations and mortality rates in the nonscorched plots across the last four sample intervals. Scorching significantly reduced fine root biomass. The influence of soil herbivores on fine root carbon allocation and fates could not be assessed in this study because the soil pesticide had no measurable effect on herbivorous nematode and insect larvae populations. The results of this study suggest that nitrogen increases fine root mortality via an increase in fine root carbon sink strength rather than a decrease in carbon allocation to fine roots. These findings support the constant allocation hypothesis regarding nitrogen controls on fine root carbon allocation and transfers in forest ecosystems. FOR. SCI. 50(2):177–187.

Carboxanilide Persistence in Wildlife: Excretion and Retention in a Rat Model - S. C. Mitchell; R. H. Waring (Bulletin of Environmental Contamination and Toxicology, 2004)

p16 Expression in Squamous Lesions of the Female Genital Tract - Mary M. Finegan; Aaron C. Han; Mitchell I. Edelson; Norman G. Rosenblum (Journal of Molecular Histology, 2004)

Extensive chloroplast haplotype variation indicates Pleistocene hybridization and radiation of North American Arabis drummondii , A. × divaricarpa , and A. holboellii (Brassicaceae) - C. H. Dobeš; T. Mitchell‐Olds; M. A. Koch (Molecular Ecology, 2004)
Arabis drummondii , A. holboellii and their hybrid A. × divaricarpa are widespread perennials of open habitats in North America. A phylogenetic analysis based on noncoding chloroplast DNA sequences ( trn L intron and trn L/F intergenic spacer) resolved A. drummondii as a monophyletic taxon, but found A. holboellii to bear chloroplast haplotypes from highly diverged evolutionary lineages. This raised the question of a possible polyphyletic origin of A. holboellii . Arabis × divaricarpa was found to be of recent and polytopic origin, a result consistent with its presumed hybrid origin. One hundred and three chloroplast haplotypes were detected within 719 Arabis accessions investigated. The majority of chloroplast‐types were estimated to have arisen prior to the Wisconsin glaciation. Phylogeographical analysis using nested clade analysis, suggested for A. holboellii (i) past fragmentation events, partitioning genetic variation in several instances between the Sierra Nevada, the Southern Rocky Mountains and the Colorado Plateau on the one hand and the Central to Northern Rockies of the United States and adjacent Cascades on the other; and for both parental species (ii) recolonization of major areas formerly covered by the Wisconsin glaciation by three haplotypes; and (iii) restricted gene flow indicating isolation by distance in areas south of the last glacial maximum. Arabis × divaricarpa is closely codistributed with its parental species and resampled their haplotypes. The highest genetic diversity was found in the Rocky Mountains from Idaho and Montana south to Utah and Colorado. This area was further hypothesized to have played a major role in the origin of both parental species and probably represented an important glacial refugium. However, evidence for glacial refugia was also found in arctic and boreal regions of Alaska and near the Great Lakes. In comparison to nuclear ribosomal internal transcribed spacer data, chloroplast DNA divergence was very high and evidently predated the origin of A. drummondii and possibly A. holboellii . Divergence of major chloroplast lineages dates back to the middle of the Pleistocene at least. Extensive hybridization is the most likely evolutionary factor working on A. holboellii to explain the revealed discrepancy in nuclear DNA and chloroplast DNA diversification.

Aerodynamic particle size analysis of aerosols from pressurized metered-dose inhalers: Comparison of andersen 8-stage cascade impactor, next generation pharmaceutical impactor, and model 3321 aerodynamic particle sizer aerosol spectrometer - Jolyon P. Mitchell; Mark W. Nagel; Kimberly J. Wiersema; Cathy C. Doyle (AAPS PharmSciTech, 2003)

Designing Effective Marine Protected Areas in Seaflower Biosphere Reserve, Colombia, Based on Biological and Sociological Information - A. FRIEDLANDER; J. SLADEK NOWLIS; J. A. SANCHEZ; R. APPELDOORN; P. USSEGLIO; C. McCORMICK; S. BEJARANO; A. MITCHELL‐CHUI (Conservation Biology, 2003)
Ecologists have paid increasing attention to the design of marine protected areas (MPAs), and their design advice consistently recommends representing all habitat types within MPAs or MPA networks as a means to provide protection to all parts of the natural ocean system. Recent developments of new habitat‐mapping techniques make this advice more achievable, but the success of such an approach depends largely on our ability to define habitat types in a way that is ecologically relevant. We devised and tested the ecological relevance of a set of habitat‐type definitions through our participation in a stakeholder‐driven process to design a network of MPAs, focusing on no‐take marine reserves in the Seaflower Biosphere Reserve, San Andrés Archipelago, Colombia. A priori definitions of habitat types were ecologically relevant, in that our habitat‐type definitions corresponded to identifiable and unique characteristics in the ecological communities found there. The identification of ecological pathways and connectivity among habitats also helped in designing ecologically relevant reserve boundaries. Our findings contributed to the overall design process, along with our summary of other general principles of marine reserve design. Extensive stakeholder input provided information concerning the resources and their patterns of use. These inputs also contributed to the reserve design process. We anticipate success for the Seaflower Biosphere Reserve at achieving conservation and social goals because its zoning process includes detailed yet flexible scientific advice and the participation of stakeholders at every step .

Radiation hybrid mapping of the canine type I and type IV collagen gene subfamilies - Jennifer K. Lowe; Richard Guyon; Melissa L. Cox; Dianne C. Mitchell; Amy L. Lonkar; Frode Lingaas; Catherine Andr; Francis Galibert; Elaine A. Ostrander; Keith E. Murphy (Functional & Integrative Genomics, 2003)

Common actions of adenosine receptor agonists in modulating human trabecular meshwork cell transport - J. C. Fleischhauer; C. H. Mitchell; W. D. Stamer; M. O. Karl; K. Peterson-Yantorno; M. M. Civan (The Journal of Membrane Biology, 2003)

Anthropogenic climate change for 1860 to 2100 simulated with the HadCM3 model under updated emissions scenarios - T. C. Johns; J. M. Gregory; W. J. Ingram; C. E. Johnson; A. Jones; J. A. Lowe; J. F. B. Mitchell; D. L. Roberts; D. M. H. Sexton; D. S. Stevenson; S. F. B. Tett; M. J. Woodage (Climate Dynamics, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

The effect of ocean dynamics in a coupled GCM simulation of the Last Glacial Maximum - C. Hewitt; R. Stouffer; A. Broccoli; J. Mitchell; Paul J. Valdes (Climate Dynamics, 2003)

Herpes Simplex Virus-1 and Varicella-Zoster Virus Latency in Ganglia - Bradley M Mitchell; David C Bloom; Randall J Cohrs; Donald H Gilden; Peter GE Kennedy (Journal of NeuroVirology, 2003)

Heavy Metal Concentrations in Fish from a Pristine Rainforest Valley in Peru: A Baseline Study Before the Start of Oil-Drilling Activities - A. C. Gutleb; A. Helsberg; C. Mitchell (Bulletin of Environmental Contamination and Toxicology, 2002)

Precision of Neural Timing: Effects of Convergence and Time-Windowing - Michael C. Reed; Jacob J. Blum; Colleen C. Mitchell (Journal of Computational Neuroscience, 2002)

Biotransformation of 10-deoxoartemisinin to its 7β-hydroxy derivative by Mucor ramannianus - Sorele Fiaux de Medeiros; Mitchell A. Avery; Bonnie Avery; Selma G.F. Leite; Antonio Carlos C. Freitas; John S. Williamson (Biotechnology Letters, 2002)

Nitroxides as antioxidants: Tempol protects against EO9 cytotoxicity - Ayelet M. Samuni; William DeGraff; Murali C. Krishna; James B. Mitchell (Molecular and Cellular Biochemistry, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Evaluation of Hbr (MITE) markers for assessment of genetic relationships among maize (Zea mays L.) inbred lines - A. M. Casa; S. E. Mitchell; O. S. Smith; J. C. Register III; S. R. Wessler; S. Kresovich (Theoretical and Applied Genetics, 2002)

Use of Stable Isotope Ratios for Evaluating Sulfur Sources and Losses at the Hubbard Brook Experimental Forest - M. J. Mitchell; B. Mayer; S. W. Bailey; J. W. Hornbeck; C. Alewell; C.T. Driscoll; G.E. Likens (Water, Air, & Soil Pollution, 2001)

The impact of dynamic sea-ice on the climatology and climate sensitivity of a GCM: a study of past, present, and future climates - C. D. Hewitt; C. A. Senior; J. F. B. Mitchell (Climate Dynamics, 2001)

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)

Classifying tree planters and non planters in a subsistence farming system using a discriminant analytical approach - A. K. Mahapatra; C. P. Mitchell (Agroforestry Systems, 2001)

Response of wheat canopy CO 2 and water gas‐exchange to soil water content under ambient and elevated CO 2 - Rowan A. C. Mitchell; Valerie J. Mitchell; David W. Lawlor (Global Change Biology, 2001)
The nature of the interaction between drought and elevated CO 2 partial pressure (pC a ) is critically important for the effects of global change on crops. Some crop models assume that the relative responses of transpiration and photosynthesis to soil water deficit are unaltered by elevated pC a , while others predict decreased sensitivity to drought at elevated pC a . These assumptions were tested by measuring canopy photosynthesis and transpiration in spring wheat (cv. Minaret) stands grown in boxes with 100 L rooting volume. Plants were grown under controlled environments with constant light (300 µmol m −2 s −1 ) at ambient (36 Pa) or elevated (68 Pa) pC a and were well watered throughout growth or had a controlled decline in soil water starting at ear emergence. Drought decreased final aboveground biomass (−15%) and grain yield (−19%) while elevated pC a increased biomass (+24%) and grain yield (+29%) and there was no significant interaction. Elevated pC a increased canopy photosynthesis by 15% on average for both water regimes and increased dark respiration per unit ground area in well‐watered plants, but not drought‐grown ones. Canopy transpiration and photosynthesis were decreased in drought‐grown plants relative to well‐watered plants after about 20–25 days from the start of the drought. Elevated pC a decreased transpiration only slightly during drought, but canopy photosynthesis continued to be stimulated so that net growth per unit water transpired increased by 21%. The effect of drought on canopy photosynthesis was not the consequence of a loss of photosynthetic capacity initially, as photosynthesis continued to be stimulated proportionately by a fixed increase in irradiance. Drought began to decrease canopy transpiration below a relative plant‐available soil water content of 0.6 and canopy photosynthesis and growth below 0.4. The shape of these responses were unaffected by pC a , supporting the simple assumption used in some models that they are independent of pC a .

Associations between smoking and adenocarcinomas and squamous cell carcinomas of the uterine cervix (United States) - James V. Lacey; Morten Frisch; Louise A. Brinton; Fouad M. Abbas; Willard A. Barnes; Patti E. Gravitt; Mitchell D. Greenberg; Sarah M. Greene; Olympia C. Hadjimichael; Larry McGowan; Rodrigue Mortel; Peter E. Schwartz; et al. (Cancer Causes & Control, 2001)

The relationship between Y chromosome DNA haplotypes and Y chromosome deletions leading to male infertility - L. Quintana-Murci; C. Krausz; E. Heyer; J. Gromoll; I. Seifer; D.E. Barton; T. Barrett; N.E. Skakkebaek; E. Rajpert-De Meyts; M. Mitchell; A.C. Lee; M.A. Jobling; et al. (Human Genetics, 2001)

Optimal detection and attribution of climate change: sensitivity of results to climate model differences - G. C. Hegerl; P. A. Stott; M. R. Allen; J. F. B. Mitchell; S. F. B. Tett; U. Cubasch (Climate Dynamics, 2000)

Multiple recombination events near the 3′ boundary of the human IgH locus duplication - Edward E. Max; Mary Mitchell; Frederick C. Mills (Mammalian Genome, 2000)

The dopamine D3/2 agonist 7-OH-DPAT attenuates the development of morphine tolerance but not physical dependence in rats - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Modulatory effects of dopamine D3/2 agonists on kappa opioid-induced antinociception and diuresis in the rat - Charles D. Cook; Andrew C. Barrett; Chockeo Syvanthong; Mitchell J. Picker (Psychopharmacology, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

Modelling the recent historical impacts of atmospheric CO 2 and climate change on Mediterranean vegetation - C. P. Osborne; P. L. Mitchell; J. E. Sheehy; F. I. Woodward (Global Change Biology, 2000)
Summary During the past century, annual mean temperature has increased by 0.75°C and precipitation has shown marked variation throughout the Mediterranean basin. These historical climate changes may have had significant, but presently undefined, impacts on the productivity and structure of sclerophyllous shrubland, an important vegetation type in the region. We used a vegetation model for this functional type to examine climate change impacts, and their interaction with the concurrent historical rise in atmospheric CO 2 . Using only climate and soil texture as data inputs, model predictions showed good agreement with observations of seasonal and regional variation in leaf and canopy physiology, net primary productivity (NPP), leaf area index (LAI) and soil water. Model simulations for shrubland sites indicated that potential NPP has risen by 25% and LAI by 7% during the past century, although the absolute increase in LAI was small. Sensitivity analysis suggested that the increase in atmospheric CO 2 since 1900 was the primary cause of these changes, and that simulated climate change alone had negative impacts on both NPP and LAI. Effects of rising CO 2 were mediated by significant increases in the efficiency of water‐use in NPP throughout the region, as a consequence of the direct effect of CO 2 on leaf gas exchange. This increase in efficiency compensated for limitation of NPP by drought, except in areas where drought was most severe. However, while water was used more efficiently, total canopy water loss rose slightly or remained unaffected in model simulations, because increases in LAI with CO 2 counteracted the effects of reduced stomatal conductance on transpiration. Model simulations for the Mediterranean region indicate that the recent rise in atmospheric CO 2 may already have had significant impacts on productivity, structure and water relations of sclerophyllous shrub vegetation, which tended to offset the detrimental effects of climate change in the region.

The simulation of SST, sea ice extents and ocean heat transports in a version of the Hadley Centre coupled model without flux adjustments - C. Gordon; C. Cooper; C. A. Senior; H. Banks; J. M. Gregory; T. C. Johns; J. F. B. Mitchell; R. A. Wood (Climate Dynamics, 2000)

Body Temperature Changes in Free-ranging Baboons (Papio hamadryas ursinus) in the Namib Desert, Namibia - C. Brain; D. Mitchell (International Journal of Primatology, 1999)

Selective attenuation of the antinociceptive effects of μ opioids by the putative dopamine D 3 agonist 7-OH-DPAT - C. D. Cook; J. S. Rodefer; Mitchell J. Picker (Psychopharmacology, 1999)

Uncertainty Analysis of Regional Mercury Exposure - C. Seigneur; K. Lohman; P. Pai; K. Heim; D. Mitchell; L. Levin (Water, Air, & Soil Pollution, 1999)

Towards the Construction of Climate Change Scenarios - John F. B. Mitchell; T. C. Johns; M. Eagles; W. J. Ingram; R. A. Davis (Climatic Change, 1999)

Phylogenetic relationships of species of Gingidia and related genera (Apiaceae, subfamily Apioideae) - A. D. Mitchell; C. J. Webb; S. J. Wagstaff (New Zealand Journal of Botany, 1998)
Five genera of Australasian apioid Apiaceae (Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla) have a complex taxo‐nomic history with the circumscription of, and inferred relationships among, the currently accepted genera based on only morphological characters. This molecular and phylogenetic study focuses on the relationships among the taxa currently included within Gingidia using the other genera as outgroups. Phylogenetic analyses of nuclear ribosomal DNA internal transcribed spacer region sequences for 17 species from these genera, and comparison with Smyrnium to root the trees, indicate that Gingidia is polyphyletic as currently circumscribed, the species belonging in two distinct monophyletic groups. However, morphological characters do not support these two groups, making taxonomic interpretation difficult. The monophyletic G. montana group includes the ditypic endemic genera Scandia and Lignocarpa, suggesting that they should not be maintained. The second monophyletic group includes G. decipiens and G. flabellata with species of Anisotome. Although our sampling of Anisotome and Aciphylla is limited, nothing in the analysis of the molecular data is inconsistent with earlier suggestions, based on morphological data, that Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla form a monophyletic group.

Fault scarp statistics at the Galapagos spreading centre from Deep Tow data - Neil C. Mitchell; Roger C. Searle (Marine Geophysical Research, 1998)

Dopaminergic activity and the discriminative stimulus effects of mu opioids in pigeons: importance of training dose and attenuation by the D 3 agonist (±)-7-OH-DPAT - C. D. Cook; Mitchell J. Picker (Psychopharmacology, 1998)

Multi-fingerprint direction and attribution analysis of greenhouse gas, greenhouse gas-plus-aerosol and solar forced climate change - G. C. Hegerl; K. Hasselmann; U. Cubasch; J. F. B. Mitchell; E. Roeckner; R. Voss; J. Waszkewitz (Climate Dynamics, 1997)

Radiative forcing and response of a GCM to ice age boundary conditions: cloud feedback and climate sensitivity - C. D. Hewitt; J. F. B. Mitchell (Climate Dynamics, 1997)

Multi-fingerprint detection and attribution analysis of greenhouse gas, greenhouse gas-plus-aerosol and solar forced climate change - G. C. Hegerl; K. Hasselmann; U. Cubasch; J. F. B. Mitchell; E. Roeckner; R. Voss; J. Waszkewitz (Climate Dynamics, 1997)

Global and regional variability in a coupled AOGCM - S. F. B. Tett; T. C. Johns; J. F. B. Mitchell (Climate Dynamics, 1997)

An evaluation of the utility of SSR loci as molecular markers in maize (Zea mays L.): comparisons with data from RFLPS and pedigree - J. S. C. Smith; E. C. L. Chin; H. Shu; O. S. Smith; S. J. Wall; M. L. Senior; S. E. Mitchell; S. Kresovich; J. Ziegle (Theoretical and Applied Genetics, 1997)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Northern Bobwhite Egg Hatchability and Chick Immunocompetence Following a Field Application of Clopyralid - C. B. Dabbert; R. B. Mitchell; D. T. Oberheu (Bulletin of Environmental Contamination and Toxicology, 1997)

New approaches to lifetime-resolved luminescence imaging - C. G. Morgan; A. C. Mitchell; J. G. Murray; E. J. Wall (Journal of Fluorescence, 1997)

A study of feral carp, Cyprinus carpio L., exposed to Microcystis aeruginosa at Lake Mokoan, Australia, and possible implications for fish health - C R Carbis; G T Rawlin; P Grant; G F Mitchell; J W Anderson; I McCauley (Journal of Fish Diseases, 1997)
Feral carp, Cyprinus carpio L., were collected at bimonthly intervals for 12 months from Lake Wellington, where there was no evidence of significant growth of Microcystis aeruginosa . Various blood parameters of these carp were measured to ascertain the normal range values for feral carp in this region. A similar study was conducted at Lake Mokoan, where M. aeruginosa formed a visible scum that contained detectable levels of microcystins for 4 consecutive months. Carp were taken from Lake Mokoan each month, and the histology and blood biochemistry of the fish were examined for indications of microcystin toxicity. During February, March and April, 66% of the carp from Lake Mokoan had livers with widespread hepatocyte atrophy, and 37% of the fish had gills with pinpoint necrosis, epithelial ballooning, folded lamellar tips and exfoliation of the lamellar epithelium. Compared to carp from Lake Wellington, the serum aspartate aminotransferase activity and the serum bilirubin concentrations of carp from Lake Mokoan were elevated during January, February, March and April. The data were consistent with impaired hepatocyte function in some carp from Lake Mokoan. Serum sodium and chloride concentrations in carp from Lake Mokoan were lower than those for carp at Lake Wellington from December to April, indicating that most carp from Lake Mokoan had difficulty maintaining cation‐anion homeostasis during this period. Nevertheless, carp at Lake Mokoan always appeared healthy, and no mortalities were reported.

The second Hadley Centre coupled ocean-atmosphere GCM: model description, spinup and validation - T. C. Johns; R. E. Carnell; J. F. Crossley; J. M. Gregory; J. F. B. Mitchell; C. A. Senior; S. F. B. Tett; R. A. Wood (Climate Dynamics, 1997)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Environmental contaminants in redheads wintering in coastal Louisiana and Texas - T. C. Michot; T. W. Custer; A. J. Nault; C. A. Mitchell (Archives of Environmental Contamination and Toxicology, 1994)

Characterization of a new thermophilic sulfate-reducing bacterium - E. A. Henry; R. Devereux; J. S. Maki; C. C. Gilmour; C. R. Woese; L. Mandelco; R. Schauder; C. C. Remsen; R. Mitchell (Archives of Microbiology, 1994)

Characterization of a new thermophilic sulfate-reducing bacterium. Thermodesulfovibrio yellowstonii , gen. nov. and sp. nov.: its phylogenetic relationship to Thermodesulfobacterium commune and their origins deep within the bacterial domain - E. A. Henry; R. Devereux; J. S. Maki; C. C. Gilmour; L. Mandelco; R. Schauder; C. C. Remsen; C. R. Woese; R. Mitchell (Archives of Microbiology, 1994)

Mutagenicity of potential effluents from an experimental low btu coal gasifier - J. M. Benson; C. E. Mitchell; R. E. Royer; C. R. Clark; R. L. Carpenter; G. J. Newton (Archives of Environmental Contamination and Toxicology, 1982)

Toxicological characterization of the process stream from an experimental low Btu coal gasifier - J. M. Benson; J. O. Hill; C. E. Mitchell; G. J. Newton; R. L. Carpenter (Archives of Environmental Contamination and Toxicology, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Parasites ofSpodoptera exigua, S. eridania [Lep.: Noctuidae] andHerpetogramma bipunctalis [Lep.: Pyralidae] collected fromAmaranthus hybridus in field corn - F. C. Tingle; T. R. Ashley; E. R. Mitchell (BioControl, 1978)

Sectional notes - L. M. Ware; M. A. Lindsay; W. B. Ward; H. A. Reiley; A. G. Tolaas; Marx Koehnke; John C. Campbell; Robert Schmidt; Earl B. Tussing; K. W. Lauer; Mitchell Jenkins; John Noonan; et al. (American Journal of Potato Research, 1941)

Sectional notes - L. M. Ware; Geo D. Ruehle; J. G. Richard; J. C. Campbell; E. V. Hardenbueg; C. A. Henderson; Robert Schmidt; J. Mitchell Jenkins; John Noonan (American Journal of Potato Research, 1941)

Sectional notes - M. A. Lindsay; E. Marx; E. R. Bennett; C. L. Fitch; A. A. Henderson; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1941)